Pressure sensitive adhesive sheet

The adhesive sheet with a fibrous substrate and dispersed black pigment maintains high blackness and resistance to peeling on curved surfaces and in harsh environments, addressing the challenges of appearance and durability.

JP2025012415APending Publication Date: 2025-01-24NITTO DENKO CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023115229
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-13
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing adhesive sheets struggle to maintain high blackness and resistance to peeling when applied to curved surfaces and exposed to harsh environments, such as high temperature and humidity, while also ensuring a good appearance without impairing the adherend's appearance.

Method used

The adhesive sheet is designed with a fibrous substrate and an adhesive layer containing a dispersed black pigment, where the adhesive layer has a density of 0.4 g/cm³ and a blackness value of less than 10, and is formulated to maintain a minimum SS breakdown strength of 0.70 MPa or more after high-temperature and high-humidity storage.

Benefits of technology

The adhesive sheet achieves high blackness, stable adhesion to curved surfaces, and maintains resistance to peeling even in harsh environments, ensuring a good appearance and long-term performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025012415000001_ABST
    Figure 2025012415000001_ABST
Patent Text Reader

Abstract

To provide a pressure sensitive adhesive sheet equipped with a base material, capable of imparting an excellent appearance based on high blackness thereof, and capable of stability maintaining excellent repulsion resistance.SOLUTION: A pressure sensitive adhesive sheet includes a fiber base material and an adhesive layer disposed at least on one side of the fiber base material. In the pressure sensitive adhesive sheet, a density of the fiber base material is 0.4 g / cm3 or less. In the adhesive layer, L* stipulated by an L*a*b* colorimetric system is 10 or lower. In the adhesive layer, a breaking strength is 0.70 to 1.10 MPa in a tensile test executed in a condition at 23°C with a tensile speed of 50 mm / min, after being held for 4 weeks under a 60°C and 90%RH environment.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pressure-sensitive adhesive sheet. [Background technology]

[0002] Generally, adhesives (also called pressure-sensitive adhesives; the same applies below) have the property of being in a soft solid (viscoelastic) state in a temperature range near room temperature and easily adhering to an adherend by pressure. Taking advantage of such properties, adhesives are widely used in various industrial fields such as home appliances, automobiles, and office automation equipment as a joining means with good workability and high adhesive reliability. A representative composition of an adhesive is a composition containing a polymer that exhibits rubber elasticity at room temperature as a base polymer. In addition, for example, adhesive sheets having a colored adhesive layer are used for the purpose of preventing light leakage from light sources such as backlight modules of liquid crystal display devices in electronic devices and self-emitting elements such as organic EL (electroluminescence), concealing the adherend, adjusting the appearance of the adherend, and designing. Patent Document 1 is an example of a document disclosing this type of technology. Patent Document 2 is a technical document disclosing an adhesive containing a styrene-based block copolymer as a base polymer. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2020-007500 A [Patent Document 2] JP 2015-28130 A Summary of the Invention [Problem to be solved by the invention]

[0004] The colored adhesive is used for the above-mentioned light blocking, covering the surface of the adherend to conceal the adherend, adjusting the appearance, imparting design, etc., and can also be used in a form in which it is colored to match the color of the adherend so that it is not noticeable when attached to the adherend. Such an adhesive is preferable because it does not impair the appearance of the adherend when used in a place where the adhesive is visible. For example, L * a * b * L defined in the color system * Add black pigment to the adhesive used to bond black parts with low L value to create an adhesive with the same L value as the parts. * By providing this value, the presence of the adhesive becomes less noticeable, and the appearance of the members bonded by the adhesive and the product including the members can be well maintained.

[0005] In addition, some of the objects to which the adhesive is to be applied have curved shapes, such as three-dimensional shapes, for example, for design or functionality. An adhesive that is applied to a part having such a curved shape is required to have the ability to follow and adhere well to the curved shape and maintain such adhesion for a long period of time, typically repulsion resistance. When the above-mentioned colored adhesive is used by being applied to a curved surface, it is also required to have repulsion resistance so that it does not peel off from the curved surface. However, when the blackness of the above-mentioned colored adhesive is increased, it may be difficult to achieve both blackness and repulsion resistance. Specifically, in order to efficiently increase the blackness of the colored adhesive, it is desirable to blend the black pigment into the adhesive in a state where it is well dispersed in a dispersion medium such as a liquid resin in advance. However, the dispersion medium causes a decrease in repulsion resistance, and for example, the above-mentioned L * If the design is made with a high degree of blackness, such that the value is 10 or less, the repulsion resistance may decrease.

[0006] By the way, the adhesive sheet is used in the form of a substrate-attached adhesive sheet having a supporting substrate according to the purpose and the place of use. For example, substrate-attached adhesive sheets tend to have excellent processability, and are preferably used for applications in which they are processed into various shapes. In addition, for example, in a thin adhesive sheet, the handleability can be improved by having a substrate. However, for example, an adhesive sheet having a resin film substrate is likely to have reduced flexibility and repulsion resistance due to the rigidity of the resin film. In a substrate-attached adhesive sheet, the ability to follow the adherend can be improved by using a fibrous substrate such as a nonwoven fabric. In addition, in order to improve the repulsion resistance, it is necessary to take measures such as selecting a fibrous material with good adhesive impregnation. Furthermore, the properties of the fibrous substrate, such as adhesive impregnation, also affect the color of the adhesive sheet. In a fibrous substrate with poor adhesive impregnation, the air present in the non-impregnated part is likely to cause whiteness, and the blackness is likely to decrease.

[0007] Furthermore, adhesives usually deteriorate to varying degrees when stored in harsh environments such as exposed to high temperature and high humidity, when the adhesive is used in such environments, or when stored or used for a long period of time. Specifically, when the adhesive is stored in harsh environments such as high temperature and high humidity, it may deteriorate and not be able to exhibit the desired characteristics. In addition, when the adhesive is exposed to such harsh environments after being attached to an adherend, the adhesive may deteriorate during use and may not be able to maintain the desired characteristics. When the adhesive deteriorates in this way, the repulsion resistance is likely to decrease significantly. In addition, in the adhesive sheet having the above-mentioned fibrous substrate, it is necessary to consider that the adhesive impregnation affects the retention of repulsion resistance. Specifically, for example, when a fibrous substrate with low adhesive impregnation is used, the influence is not apparent at the beginning and the adhesive has good repulsion resistance, but when the adhesive is exposed to a high temperature and high humidity environment or deteriorated due to long-term use, the low adhesive impregnation into the fibrous substrate may become apparent as a decrease in repulsion resistance. For example, many home appliances have long product life, and PSA sheets used in such applications are required to have temporal stability that allows them to maintain their PSA sheet performance even when exposed to high temperature and high humidity environments. For example, in applications requiring a certain level of repulsion resistance, the PSA sheet is required to have the ability to stably maintain the repulsion resistance for a long period of time.

[0008] The present invention has been created in consideration of the above circumstances, and aims to provide an adhesive sheet that has a substrate and can impart a good appearance based on a high degree of blackness while stably maintaining good repulsion resistance. [Means for solving the problem]

[0009] According to the present specification, there is provided a pressure-sensitive adhesive sheet comprising a fibrous base material and a pressure-sensitive adhesive layer provided on at least one surface of the fibrous base material. In this pressure-sensitive adhesive sheet, the density of the fibrous base material is 0.4 g / cm 3 The pressure-sensitive adhesive layer is L * a * b * L defined in the color system *The adhesive layer has a breaking strength (SS breaking strength after storage at high temperature and high humidity) of 0.70 MPa or more and 1.10 MPa or less in a tensile test carried out under conditions of 23°C and a tensile speed of 50 mm / min after being kept in an environment of 60°C and 90% RH for 4 weeks. * Since the thickness is 10 or less, the adhesive layer can have a good appearance based on the high blackness in the configuration including the fibrous substrate. Furthermore, the adhesive sheet can stably maintain good repulsion resistance even when exposed to a harsh environment based on the selection of the fibrous substrate and the SS breaking strength property after high temperature and high humidity storage of the adhesive layer. In short, the adhesive sheet having the above configuration can achieve both a good appearance based on the blackness and stable maintenance of repulsion resistance in the configuration including the substrate.

[0010] In some embodiments, the pressure-sensitive adhesive layer contains a black pigment dispersion. By incorporating the black pigment in the form of a dispersion into the pressure-sensitive adhesive layer, a high degree of blackness that can impart a good appearance is easily obtained. In some preferred embodiments, the black pigment dispersion contains a black pigment and a liquid resin. In the dispersion, at least a part of the black pigment is dispersed in the liquid resin. With this configuration, a high degree of blackness is easily obtained. In addition, in a composition in which the black pigment dispersion is incorporated, the SS breaking strength of the pressure-sensitive adhesive layer after high-temperature and high-humidity storage is set within a specific range, whereby both blackness and repulsion resistance can be preferably achieved.

[0011] In some embodiments, the blending amount of the black pigment dispersion is 4 parts by weight or more and 10 parts by weight or less based on non-volatile content, relative to 100 parts by weight of the base polymer contained in the pressure-sensitive adhesive layer. * It is easy to reduce the value to 10 or less. In addition, by making the blending amount of the black pigment dispersion equal to or less than a predetermined amount, it is easy to adjust the SS breaking strength property after high temperature and high humidity storage to within a specific range, and it is easy to obtain excellent repulsion resistance.

[0012] In some embodiments, the pressure-sensitive adhesive layer contains a rubber-based polymer as a base polymer. The effects of the technology disclosed herein (specifically, stable retention of repulsion resistance) can be preferably exhibited in an embodiment having a pressure-sensitive adhesive layer containing a rubber-based polymer as a base polymer. In some preferred embodiments, the pressure-sensitive adhesive layer contains a styrene-based block copolymer as a base polymer. A pressure-sensitive adhesive containing a styrene-based block copolymer can better balance adhesive strength and cohesive strength, making it easy to design a pressure-sensitive adhesive layer with excellent repulsion resistance.

[0013] In some embodiments, the pressure-sensitive adhesive layer is a pressure-sensitive adhesive layer formed from a solvent-based pressure-sensitive adhesive composition or a hot-melt pressure-sensitive adhesive composition. The technology disclosed herein is preferably implemented in a configuration including a pressure-sensitive adhesive layer made of a solvent-based or hot-melt pressure-sensitive adhesive.

[0014] In some embodiments, the thickness of the fibrous base material is 20 μm or more and 60 μm or less. The technology disclosed herein is preferably carried out in an embodiment using a fibrous base material having a thickness in the above range.

[0015] In some embodiments, the total thickness of the pressure-sensitive adhesive sheet is 100 μm or more and 350 μm or less. The technology disclosed herein is preferably carried out in an embodiment using a pressure-sensitive adhesive sheet having a thickness in the above range.

[0016] The adhesive sheet disclosed herein is preferably used in a form in which it is attached to an area including a curved surface of an adherend having a curved surface. In such a use form, the adhesive sheet is required to stably exhibit repulsion resistance that does not peel off from the curved surface, so it is desirable to apply the adhesive sheet disclosed herein. In addition, when the adherend is a black adherend, due to the high blackness of the adhesive layer, the adhesive sheet is not noticeable on the adherend to which the adhesive sheet is attached, and the appearance is not impaired. [Brief description of the drawings]

[0017] [Figure 1]FIG. 1 is a schematic cross-sectional view showing a configuration of a pressure-sensitive adhesive sheet according to an embodiment. [Diagram 2] FIG. 2 is a schematic diagram showing the initial state of a test piece attached to an adherend in a repulsion resistance evaluation. [Diagram 3] FIG. 2 is a schematic diagram showing a state in which an end of a test piece attached to an adherend is lifted up from the adherend in a repulsion resistance evaluation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] A preferred embodiment of the present invention will be described below. Note that matters other than those specifically mentioned in this specification and necessary for carrying out the present invention can be understood by a person skilled in the art based on the teachings on carrying out the invention described in this specification and the common general technical knowledge at the time of filing. The present invention can be carried out based on the contents disclosed in this specification and the common general technical knowledge in the field. In addition, in the following drawings, components and parts having the same function may be described by using the same reference numerals, and duplicated descriptions may be omitted or simplified. In addition, the embodiments described in the drawings are schematic to clearly explain the present invention, and do not accurately represent the size or scale of the product actually provided.

[0019] In this specification, the term "adhesive" refers to a material that exhibits a soft solid (viscoelastic) state in the temperature range around room temperature and has the property of easily adhering to an adherend by pressure, as described above. The adhesive referred to here is generally a material having a complex tensile modulus E * (1Hz)<10 7 dyne / cm 2 The material may be a material having the above properties at 25° C.

[0020] In this specification, the "base polymer" of a pressure-sensitive adhesive refers to the main component of the rubbery polymer (a polymer that exhibits rubber elasticity in a temperature range around room temperature) contained in the pressure-sensitive adhesive, and typically refers to a component that accounts for more than 50% by weight of the rubbery polymer.

[0021] In this specification, the term "styrene-based block copolymer" refers to a polymer having at least one styrene block. The above-mentioned styrene block refers to a segment having styrene as the main monomer. A segment consisting essentially of styrene is a typical example of the styrene block referred to here. In addition, the term "styrene-isoprene block copolymer" refers to a polymer having at least one styrene block and at least one isoprene block (a segment having isoprene as the main monomer). Representative examples of the styrene-isoprene block copolymer include a copolymer (triblock body) having a triblock structure in which a styrene block (hard segment) is at each end of an isoprene block (soft segment), and a copolymer (diblock body) having a diblock structure consisting of one isoprene block and one styrene block. The term "styrene-butadiene block copolymer" refers to a polymer having at least one styrene block and at least one butadiene block (a segment having butadiene as the main monomer).

[0022] In this specification, the "styrene content" of a styrene-based block copolymer refers to the weight ratio of the styrene component to the total weight of the block copolymer. The styrene content can be measured by NMR (nuclear magnetic resonance spectroscopy). The proportion of the diblock monomer in the styrene-based block copolymer (hereinafter sometimes referred to as the "diblock monomer ratio" or "diblock ratio") is determined by the following method. That is, the styrene-based block copolymer is dissolved in tetrahydrofuran (THF), and a total of four liquid chromatography columns, GS5000H and G4000H manufactured by Tosoh Corporation, are connected in series, each with two columns, and high performance liquid chromatography is performed under conditions of a temperature of 40°C and a flow rate of 1 mL / min using THF as the mobile phase. The peak area corresponding to the diblock monomer is measured from the obtained chart. The diblock monomer ratio is then determined by calculating the percentage of the peak area corresponding to the diblock monomer relative to the total peak area.

[0023] <Structural example of adhesive sheet> The pressure-sensitive adhesive sheet disclosed herein (which may be in a long form such as a tape) may be in the form of, for example, a double-sided pressure-sensitive adhesive sheet having a cross-sectional structure as shown in FIG. 1. This double-sided pressure-sensitive adhesive sheet 1 comprises a fibrous base material 15, a first pressure-sensitive adhesive layer 11 laminated on a first surface of the fibrous base material 15, and a second pressure-sensitive adhesive layer 12 laminated on a second surface of the fibrous base material 15. The first pressure-sensitive adhesive layer 11 and the second pressure-sensitive adhesive layer 12 are colored and have an L * a * b * L defined in the color system * The double-sided pressure-sensitive adhesive sheet 1 has a black color with a color difference of 10 or less. Before use (before attachment to an adherend), the double-sided pressure-sensitive adhesive sheet 1 may be in a form in which the front surface 21A and the back surface 21B of the double-sided pressure-sensitive adhesive sheet 1 are both release surfaces and superimposed on a release liner 21 and wound into a spiral shape, as shown in FIG. In such a form of double-sided pressure-sensitive adhesive sheet 1, the surface of the second pressure-sensitive adhesive layer 12 (second adhesive surface 12A) is protected by the front surface 21A of the release liner 21, and the surface of the first pressure-sensitive adhesive layer 11 (first adhesive surface 11A) is protected by the back surface 21B of the release liner 21. Alternatively, the first adhesive surface 11A and the second adhesive surface 12A may each be protected by two independent release liners.

[0024] The adhesive sheet disclosed herein may also be in the form of a single-sided adhesive sheet comprising a fibrous base material and an adhesive layer laminated on a first side thereof, with no adhesive layer on a second side of the fibrous base material.

[0025] In the technology disclosed herein, the release liner can be a conventional release paper or the like, and is not particularly limited. For example, a release liner having a release treatment layer on the surface of a substrate such as a plastic film or paper, or a release liner made of a low-adhesion material such as a fluorine-based polymer (polytetrafluoroethylene, etc.) or a polyolefin-based resin (polyethylene, polypropylene, etc.) can be used. The release treatment layer can be formed by surface-treating the substrate with a release treatment agent such as a silicone-based, long-chain alkyl-based, fluorine-based, or molybdenum sulfide.

[0026] <Fiber base material> The adhesive sheet disclosed herein has a structure in which an adhesive layer is laminated on a fibrous substrate. By using a fibrous material as the substrate, the adhesive sheet has good processability and handleability due to the substrate, and at the same time has moderate flexibility, so that it can follow the adherend well and improve repulsion resistance. As the fibrous substrate, woven fabrics, nonwoven fabrics, knitted fabrics, nets, etc., made by spinning various fibrous materials alone or in combination, etc., can be used. Here, the nonwoven fabric is a concept that includes nonwoven fabrics made using a general papermaking machine, such as paper, for example, Japanese paper and fine paper. The concept of the nonwoven fabric also includes felt. Examples of the fibrous material constituting the fibrous substrate include inorganic fibers such as glass fibers and carbon fibers, metal fibers, etc., in addition to natural fibers and chemical fibers (synthetic fibers) as described below. Two or more fibrous materials of different materials may be used in combination. The fibrous substrate can also be understood as a support substrate that holds the adhesive layer.

[0027] As the fibrous substrate, nonwoven fabrics can be preferably used. Examples of nonwoven fabrics include nonwoven fabrics made of natural fibers such as wood pulp, hemp pulp, cotton, hemp (e.g., Manila hemp), wool, and silk; nonwoven fabrics made of chemical fibers (synthetic fibers) such as polyester fibers such as polyethylene terephthalate (PET) fibers, rayon, vinylon, acetate fibers, polyvinyl alcohol (PVA) fibers, polyamide fibers, polyolefin fibers, and polyurethane fibers; and nonwoven fabrics made by combining two or more fibers of different materials. Among them, from the viewpoint of impregnation of the adhesive and strength, nonwoven fabrics made of paper pulp such as wood pulp and hemp pulp (e.g., hemp pulp made from Manila hemp) are preferred.

[0028] In the technology disclosed herein, the density is 0.4 g / cm 3 A fibrous base material having a density of 0.4 g / cm or less is used. Here, the density of the fibrous base material refers to the bulk density. A fibrous base material having a density in the above range is likely to provide excellent repulsion resistance. Specifically, a fibrous base material having a density of 0.4 g / cm or less is used. 3 The fibrous base material having the following properties has good impregnation with adhesive, and based on this impregnation, it is easy to obtain excellent repulsion resistance, and it is easy to maintain the repulsion resistance even when exposed to a harsh environment. In addition, since a fibrous base material with good impregnation with adhesive is less likely to have air trapped between the adhesive and the fibrous base material, the occurrence of whiteness caused by the air is suppressed. This is advantageous for realizing an appearance based on a high degree of blackness. The density of the fibrous base material is 0.44 g / cm 3 or less, 0.40 g / cm 3 In some embodiments, the density is 0.38 g / cm or less. 3 or less, 0.36 g / cm 3 Less than 0.34g / cm 3 Less than 0.32g / cm 3 Less than 0.30g / cm 3 Less than 0.28g / cm 3 Less than 0.26g / cm 3 Less than 0.24g / cm 3 The following is also fine.

[0029] The lower limit of the density of the fibrous base material is not particularly limited, and may be, for example, 0.2 g / cm3 from the viewpoint of processability and workability. 3 The density of the fibrous base material is preferably 0.15 g / cm or more. 3 or more, and may be 0.20 g / cm 3 In some embodiments, the density is 0.22 g / cm or more. 3 or more, 0.24 g / cm 3 More than 0.26g / cm 3 More than 0.28g / cm 3 More than 0.30g / cm 3 More than 0.32g / cm 3 More than 0.34g / cm 3 More than 0.36g / cm 3 More than 0.38g / cm 3 More than that is fine.

[0030] In addition, although not particularly limited, in some embodiments, the basis weight (weight per unit area) of the fibrous substrate is, for example, 25 g / m 2 Less than or equal to 20 g / m 2 In some preferred embodiments, the basis weight may be 18 g / m or less. 2 Less than or equal to 16 g / m 2 or less, 15 g / m 2 In some embodiments, the basis weight is less than 10 g / m 2 It is preferable that the thickness is 12 g / m or more. 2 More preferably, it is 14 g / m or more. 2 or more, and 2 Or more. The fibrous base material having the above basis weight tends to have a moderate strength. The technology disclosed herein can be suitably implemented by selecting and using a fibrous base material having the above basis weight range and having an appropriate density and thickness.

[0031] Although not particularly limited, in some embodiments, the thickness of the fibrous substrate may be 150 μm or less, or may be 100 μm or less. In some preferred embodiments, the thickness is 60 μm or less, preferably 50 μm or less, may be 45 μm or less, or may be 43 μm or less. When the thickness of the fibrous substrate is small, it becomes easier to impregnate the adhesive into the inside of the fibrous substrate. In addition, in some embodiments, the thickness may be 10 μm or more, or may be 15 μm or more. In some preferred embodiments, the thickness is 20 μm or more, more preferably 25 μm or more, even more preferably 30 μm or more, particularly preferably 35 μm or more, even more particularly preferably 40 μm or more, or may be 43 μm or more. By increasing the thickness of the fibrous substrate within the above range, it is possible to achieve a good balance between improving the strength of the fibrous substrate itself and impregnation of the adhesive into the inside of the fibrous substrate. The technology disclosed herein can be suitably implemented by selecting and using a fibrous base material having a thickness within the above range and an appropriate density and basis weight.

[0032] In addition to the above-mentioned fibrous materials, the fibrous substrate (e.g., nonwoven fabric) may contain a resin component, typically in a non-fibrous form, such as starch (e.g., cationic starch), polyacrylamide, viscose, polyvinyl alcohol, urea formaldehyde resin, melamine formaldehyde resin, polyamide polyamine epichlorohydrin, etc. The above-mentioned resin component may function as a paper strength enhancer for the nonwoven fabric. By using such a resin component as necessary, the strength of the fibrous substrate and the impregnation of the adhesive into the fibrous substrate can be adjusted. The fibrous substrate in the technology disclosed herein may also contain, as necessary, additives that are common in the field of manufacturing fibrous substrates (e.g., nonwoven fabrics), such as retention aids, drainage agents, viscosity modifiers, and dispersants.

[0033] <Adhesive layer> (L * ) In the technology disclosed herein, the adhesive layer constituting the adhesive sheet (in an embodiment having a first adhesive layer and a second adhesive layer, both the first adhesive layer and the second adhesive layer) is L* a * b * L defined in the color system * is 10 or less. * L * a * b * It indicates the lightness in the color system, L * The lower the value, the higher the blackness. * A pressure-sensitive adhesive layer having a value of 10 or less has a high degree of blackness, and due to this high degree of blackness, in a configuration including a fibrous base material, it is possible to impart a good appearance to the pressure-sensitive adhesive sheet as a whole. For example, * When a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer having a L of 10 or less is used for bonding a black adherend, the L approaches the color of the adherend, so that the sheet is inconspicuous when attached to the adherend and does not impair the appearance of the bonded structure. * may be 9.0 or less, 8.0 or less, 7.0 or less, 6.0 or less, 5.0 or less, 4.0 or less, 3.0 or less, 2.0 or less, or 1.0 or less. * may be 0.1 or more, 0.5 or more, 1.0 or more, 2.0 or more, 3.0 or more, 4.0 or more, 5.0 or more, 6.0 or more, or 8.0 or more. * The appropriate range is set according to the color of the adherend and the location where the adhesive sheet is applied. From the viewpoint of compatibility with adhesive properties (repulsion resistance, adhesive strength, holding power, etc.), the above L * may be a relatively high value within the range of 10 or less.

[0034] L of adhesive layer * The L of the pressure-sensitive adhesive layer can be measured by the method described in the Examples below. * can be adjusted, for example, by selecting the blending amount, type, particle size, etc. of the black pigment, and the dispersibility within the adhesive layer.

[0035] (SS breaking strength) Furthermore, the adhesive layers constituting the adhesive sheet (in an embodiment having a first adhesive layer and a second adhesive layer, both the first adhesive layer and the second adhesive layer) are characterized in that after being kept in an environment of 60°C and 90% RH for 4 weeks, the breaking strength (SS breaking strength after high temperature and high humidity storage) in a tensile test carried out under conditions of 23°C and a tensile speed of 50 mm / min is 0.70 MPa or more and 1.10 MPa or less. An adhesive having an SS breaking strength of 0.70 MPa or more after high temperature and high humidity storage is likely to retain good repulsion resistance even when exposed to a harsh environment. In particular, the above-mentioned L * When a black pigment or a component for improving the dispersibility of a black pigment is used as a means for reducing the SS breaking strength of the adhesive layer, the SS breaking strength of the adhesive layer tends to decrease. * By designing the SS breaking strength after high-temperature and high-humidity storage to be equal to or greater than a predetermined value while having a blackness of 10 or less, it is possible to obtain a pressure-sensitive adhesive that can stably maintain good repulsion resistance even when exposed to a harsh environment. In addition, by having the SS breaking strength after high-temperature and high-humidity storage of 1.10 MPa or less, the adhesive has good adhesion to the adherend surface and good conformability to curved surfaces, and these actions tend to make it easier to obtain excellent repulsion resistance. In some preferred embodiments, the SS breaking strength after high-temperature and high-humidity storage is 0.75 MPa or more, more preferably 0.80 MPa or more, may be 0.85 MPa or more, may be 0.90 MPa or more, or may be 0.92 MPa or more. In some preferred embodiments, the SS breaking strength after high-temperature and high-humidity storage is 1.05 MPa or less, more preferably 1.00 MPa or less (e.g., less than 1.00 MPa), even more preferably 0.97 MPa or less, may be 0.94 MPa or less, may be 0.90 MPa or less, or may be 0.87 MPa or less. A pressure-sensitive adhesive having a SS breaking strength after high-temperature and high-humidity storage in the above range also tends to have excellent holding power. In addition, by designing the SS breaking strength after high-temperature and high-humidity storage to be a predetermined value or less within the above range, it is possible to better achieve both high blackness and stable retention of repulsion resistance.

[0036] In some embodiments, the adhesive layer constituting the adhesive sheet (in an embodiment having a first adhesive layer and a second adhesive layer, both the first adhesive layer and the second adhesive layer) preferably has a breaking strength (initial SS breaking strength) of 0.70 MPa or more in a tensile test performed under conditions of 23°C and a tensile speed of 50 mm / min. By designing the initial SS breaking strength to be a predetermined value or more, excellent repulsion resistance can be preferably achieved. In some preferred embodiments, the initial SS breaking strength is 0.75 MPa or more, more preferably 0.80 MPa or more, more preferably 0.85 MPa or more, may be 0.90 MPa or more, or may be 0.92 MPa or more. In addition, the initial SS breaking strength is preferably 1.10 MPa or less. This provides good adhesion to the adherend surface and good conformability to curved surfaces, and these actions tend to make it easier to obtain excellent repulsion resistance. In some preferred embodiments, the initial SS breaking strength is 1.05 MPa or less, more preferably 1.00 MPa or less (e.g., less than 1.00 MPa), even more preferably 0.97 MPa or less, and may be 0.94 MPa or less, 0.90 MPa or less, or 0.87 MPa or less. A pressure-sensitive adhesive having an initial SS breaking strength in the above range also tends to have excellent holding power. In addition, by designing the initial SS breaking strength to be within the above range and below a predetermined value, it is possible to better achieve both high blackness and repulsion resistance.

[0037] Although not particularly limited, the difference (|RS1-RS0|) between the breaking strength (SS breaking strength after high temperature and high humidity storage) RS1 in the tensile test performed under the conditions of 23°C and a tensile speed of 50 mm / min after keeping in the above-mentioned 60°C 90% RH environment for 4 weeks and the breaking strength (initial SS breaking strength) RS0 in the tensile test performed under the conditions of 23°C and a tensile speed of 50 mm / min is, for example, preferably 0.30 or less, more preferably 0.20 or less, even more preferably 0.15 or less, and may be 0.10 or less. The adhesive layer in which the difference (|RS1-RS0|) is within a predetermined range has good performance stability and good stability over time even when exposed to a high temperature and high humidity environment, and therefore is likely to stably maintain the desired repulsion resistance. The lower limit of the difference (|RS1-RS0|) may be, for example, 0 or more (specifically 0.00 or more), or may be 0.05 or more.

[0038] In some embodiments, the SS breaking strength reduction rate A after high temperature and high humidity storage, which is expressed by the relational formula between the SS breaking strength RS1 after high temperature and high humidity storage and the initial SS breaking strength RS0: A=(RS0-RS1) / RS0×100, may be, for example, 30% or less, or may be 20% or less. In some preferred embodiments, the SS breaking strength reduction rate A after high temperature and high humidity storage is 15% or less, more preferably 13% or less, even more preferably 12% or less, particularly preferably 11% or less, and most preferably 10% or less. A pressure-sensitive adhesive layer having a low SS breaking strength reduction rate A after high temperature and high humidity storage has good performance stability and good stability over time even when exposed to a high temperature and high humidity environment, and therefore is likely to stably maintain the desired repulsion resistance. The lower limit of the SS breaking strength reduction rate A after high temperature and high humidity storage is not particularly limited, but may be, for example, 0% or more, and may be 5% or more in practical use.

[0039] The SS breaking strength properties (SS breaking strength after storage at high temperature and high humidity, initial SS breaking strength) are more specifically measured by the method described in the Examples below. *The compatibility of the above L and the above SS breaking strength (SS breaking strength after high temperature and high humidity storage, initial SS breaking strength) can be adjusted by selecting the type and amount of adhesive and adhesive-containing components (base polymer, tackifier resin, black pigment and its dispersion medium, other additives, etc.) based on the description in this specification. * The initial SS breaking strength of the adhesive layer having a blackness (blackness) can be designed by increasing the cohesive strength of the adhesive layer. Although not particularly limited, the degree of crosslinking can be increased by selecting the type and amount of crosslinking agent, thereby increasing the cohesive strength and therefore the initial SS breaking strength. * For a styrene block copolymer-containing adhesive having a blackness (blackness), the initial SS breaking strength can be adjusted to a predetermined range by various methods for increasing the cohesive strength of the copolymer (e.g., adjusting the styrene content), using a material that can improve the cohesive strength of the styrene phase (e.g., aromatic ring-containing tackifier resin, etc.). In addition, the SS breaking strength after high temperature and high humidity storage can be designed by adopting an adhesive composition that is less likely to deteriorate in a high temperature and high humidity environment, or by setting the initial SS breaking strength higher in consideration of the deterioration of the adhesive layer. Although not particularly limited, for example, the deterioration of the adhesive layer can be suppressed by selecting an adhesive type or base polymer type that is relatively less likely to deteriorate, blending an appropriate amount of an anti-aging agent, limiting the amount of materials that are easily deteriorated, etc., and the SS breaking strength after high temperature and high humidity storage can be adjusted to a predetermined range. The same applies to the above difference (|RS1-RS0|) and the SS breaking strength reduction rate A after high temperature and high humidity storage.

[0040] (Base polymer) In the technology disclosed herein, the type of adhesive constituting the adhesive layer (in an embodiment having a first adhesive layer and a second adhesive layer, both the first adhesive layer and the second adhesive layer. The same applies below unless otherwise specified) is not particularly limited. The adhesive may contain one or more of various rubber-like polymers such as acrylic polymers, rubber polymers (natural rubber, synthetic rubber, mixtures thereof, etc.), polyester polymers, urethane polymers, polyether polymers, silicone polymers, polyamide polymers, and fluorine polymers as base polymers that can be used in the field of adhesives. From the viewpoint of adhesive performance, cost, etc., an adhesive containing an acrylic polymer or a rubber polymer as a base polymer can be preferably used. Among them, an adhesive (rubber-based adhesive) having a rubber polymer as a base polymer is preferable. The effect of the technology disclosed herein (specifically, stable retention of repulsion resistance) can be preferably exhibited in an embodiment using a rubber-based adhesive.

[0041] In some preferred embodiments, the pressure-sensitive adhesive layer contains a styrene-based block copolymer as a base polymer. A pressure-sensitive adhesive containing a styrene-based block copolymer tends to have excellent adhesive strength and cohesive strength, and it is easy to design a pressure-sensitive adhesive having excellent repulsion resistance. As the styrene-based block copolymer, a block copolymer of styrene and a conjugated diene compound is preferably used. Specific examples of the conjugated diene compound include 1,3-butadiene and isoprene. For example, a preferred embodiment is one in which the base polymer contains at least one of a styrene-isoprene block copolymer and a styrene-butadiene block copolymer. The styrene-based block copolymer may contain a hydrogenated product in which at least a portion of the styrene-based block copolymer is hydrogenated (hydrogen atoms are added). The styrene-based block copolymer may be used alone or in combination of two or more. Of the styrene-based block copolymers contained in the pressure-sensitive adhesive layer, it is preferred that the proportion of the styrene-isoprene block copolymer is 70% by weight or more, the proportion of the styrene-butadiene block copolymer is 70% by weight or more, or the total proportion of the styrene-isoprene block copolymer and the styrene-butadiene block copolymer is 70% by weight or more. In some preferred embodiments, substantially all (e.g., 95 to 100% by weight) of the styrene-based block copolymer is a styrene-isoprene block copolymer. In other preferred embodiments, substantially all (e.g., 95 to 100% by weight) of the styrene-based block copolymer is a styrene-butadiene block copolymer.

[0042] The styrene-based block copolymer may be in the form of a diblock, triblock, radial, a mixture thereof, or the like. In the triblock and radial, it is preferable that a styrene block is arranged at the end of the polymer chain. The styrene blocks arranged at the end of the polymer chain are likely to gather together to form a styrene domain, which forms a pseudo-crosslinked structure and improves the cohesive strength of the adhesive. As the styrene-based block copolymer used in the technology disclosed herein, from the viewpoint of adhesive strength, one having a diblock ratio of 30% by weight or more can be preferably used. The diblock ratio is more preferably 40% by weight or more, even more preferably 50% by weight or more, particularly preferably 60% by weight or more, even more particularly preferably 65% ​​by weight or more, and most preferably 70% by weight or more (for example, 75% by weight or more). In addition, from the viewpoint of cohesive strength, etc., a styrene-based block copolymer having a diblock ratio of 90% by weight or less (more preferably 85% by weight or less, for example, 80% by weight or less) can be preferably used. From the viewpoint of realizing excellent repulsion resistance by applying the technology disclosed herein, a styrene-based block copolymer having a diblock ratio of 60 to 85% by weight is preferred, and a styrene-based block copolymer having a diblock ratio of 70 to 85% by weight (for example, 70 to 80% by weight) is more preferred.

[0043] The styrene content of the styrene-based block copolymer may be, for example, 5 to 40% by weight. From the viewpoint of cohesive strength, a styrene-based block copolymer having a styrene content of 10% by weight or more is usually preferred. The styrene content is more preferably more than 10% by weight, even more preferably 12% by weight or more, and particularly preferably 14% by weight or more. From the viewpoint of adhesive strength, the styrene content is preferably 35% by weight or less, more preferably 30% by weight or less, even more preferably 25% by weight or less, particularly preferably 20% by weight or less (for example, less than 20% by weight), even more particularly preferably 18% by weight or less, and may be, for example, 16% by weight or less. From the viewpoint of better exerting the effect of applying the technology disclosed herein, a styrene-based block copolymer having a styrene content of 12% by weight or more and less than 20% by weight may be preferably adopted.

[0044] (tackifier resin) In some embodiments, the adhesive layer preferably contains a tackifier resin. By including a tackifier resin in the adhesive layer, the adhesive strength can be increased. A pressure-sensitive adhesive containing a tackifier resin and having an SS breaking strength in the range of 0.70 to 1.10 MPa after storage at high temperature and high humidity can provide better repulsion resistance. As the tackifier resin, one or more types selected from various known tackifier resins such as petroleum resins, styrene-based resins, coumarone-indene resins, terpene resins, modified terpene resins, rosin-based resins, rosin derivative resins, and ketone-based resins can be used.

[0045] Examples of petroleum resins include aliphatic (C5) petroleum resins, aromatic (C9) petroleum resins, aliphatic / aromatic copolymer (C5 / C9) petroleum resins, and hydrogenated products thereof (for example, alicyclic petroleum resins obtained by hydrogenating aromatic petroleum resins).

[0046] Examples of styrene-based resins include those containing a homopolymer of styrene as the main component, those containing a homopolymer of α-methylstyrene as the main component, those containing a homopolymer of vinyltoluene as the main component, and those containing a copolymer containing two or more of styrene, α-methylstyrene, and vinyltoluene in the monomer composition as the main component (for example, an α-methylstyrene / styrene copolymer resin containing an α-methylstyrene / styrene copolymer as the main component).

[0047] The coumarone-indene resin may be a resin containing coumarone and indene as monomer components constituting the resin skeleton (main chain). Other monomer components that may be contained in the resin skeleton besides coumarone and indene include styrene, α-methylstyrene, methylindene, vinyltoluene, etc.

[0048] Terpene resins include unmodified terpene resins and modified terpene resins. Examples of terpene resins (unmodified terpene resins) include α-pinene polymers, β-pinene polymers, dipentene polymers, and the like. Examples of modified terpene resins include the above terpene resins that have been modified (phenol-modified, styrene-modified, hydrogenated, hydrocarbon-modified, and the like). Specific examples include terpene phenolic resins, styrene-modified terpene resins, and hydrogenated terpene resins. The above terpene phenolic resins include hydrogenated terpene phenolic resins.

[0049] The above-mentioned "terpene phenol resin" refers to a polymer containing a terpene residue and a phenol residue, and is a concept that includes both a copolymer of a terpene and a phenolic compound (terpene-phenol copolymer resin) and a terpene homopolymer or copolymer (terpene resin, typically an unmodified terpene resin) modified with phenol (phenol-modified terpene resin). Suitable examples of terpenes constituting the above-mentioned terpene phenol resin include monoterpenes such as α-pinene, β-pinene, and limonene (including d-, l-, and d / l-forms (dipentene)).

[0050] Specific examples of rosin-based resins include unmodified rosins (raw rosins) such as gum rosin, wood rosin, and tall oil rosin; modified rosins (hydrogenated rosin, disproportionated rosin, polymerized rosin, other chemically modified rosins, etc.) obtained by modifying these unmodified rosins through hydrogenation, disproportionation, polymerization, etc. Examples of rosin derivative resins include rosin esters such as unmodified rosin esterified with alcohols (i.e., esterified rosin), and modified rosin (hydrogenated rosin, disproportionated rosin, polymerized rosin, etc.) esterified with alcohols (i.e., esterified modified rosin); unsaturated fatty acid modified rosins obtained by modifying unmodified rosin or modified rosin (hydrogenated rosin, disproportionated rosin, polymerized rosin, etc.) with unsaturated fatty acid; and unsaturated fatty acid modified rosins obtained by modifying rosin esters with unsaturated fatty acid. Examples of the rosin esters include rosin alcohols obtained by reducing the carboxyl groups in unmodified rosin, modified rosin (hydrogenated rosin, disproportionated rosin, polymerized rosin, etc.), unsaturated fatty acid modified rosins, or unsaturated fatty acid modified rosin esters; metal salts of rosins (particularly rosin esters) such as unmodified rosin, modified rosin, and various rosin derivatives; rosin phenolic resins obtained by adding phenol to rosins (unmodified rosin, modified rosin, various rosin derivatives, etc.) using an acid catalyst and then thermally polymerizing the resulting mixture; and the like.

[0051] In some embodiments, the adhesive layer contains a tackifier resin having an aromatic ring as a tackifier resin. Aromatic ring-containing tackifier resins tend to have a high softening point, and are easy to achieve both improved adhesive strength and high cohesive strength. In addition, although not particularly limited, aromatic ring-containing tackifier resins have good compatibility with styrene block copolymers, can increase the cohesive strength of the styrene phase, and are easy to favorably exhibit the effect of adding them to styrene block copolymer-containing adhesives. Examples of aromatic ring-containing tackifier resins include the above-mentioned aromatic petroleum resins, aliphatic / aromatic copolymer petroleum resins, styrene resins, coumarone-indene resins, styrene-modified terpene resins, phenol-modified terpene resins, rosin phenol resins, etc. The aromatic ring-containing tackifier resins can be used alone or in combination of two or more.

[0052] Although not particularly limited, the softening point of the aromatic ring-containing tackifier resin is preferably higher than 100° C. From the viewpoint of improving the cohesive strength (e.g., high-temperature cohesive strength) and improving the repulsion resistance, it is preferable to use an aromatic ring-containing tackifier resin having a softening point of 120° C. or higher. The aromatic ring-containing tackifier resin having a softening point of 120° C. or higher is tackifier resin T described later. H In some embodiments, the softening point of the aromatic ring-containing tackifier resin is more preferably 125° C. or higher, further preferably 130° C. or higher, particularly preferably 135° C. or higher, and may be 145° C. or higher. From the viewpoint of adhesive strength, the softening point of the aromatic ring-containing tackifier resin is usually 200° C. or lower, preferably 180° C. or lower, and more preferably 170° C. or lower (e.g., 160° C. or lower).

[0053] In this specification, the softening point of the tackifier resin is defined as a value measured based on the softening point test method (ring and ball method) specified in JIS K5902 and JIS K2207. Specifically, the sample is melted as quickly as possible at a low temperature, and is carefully filled into a ring placed on a flat metal plate so as not to create bubbles. After cooling, the part that protrudes from the flat surface including the top end of the ring is cut off with a slightly heated knife. Next, a holder (ring stand) is placed in a glass container (heating bath) with a diameter of 85 mm or more and a height of 127 mm or more, and glycerin is poured to a depth of 90 mm or more. Next, a steel ball (diameter 9.5 mm, weight 3.5 g) and the ring filled with the sample are immersed in glycerin without touching each other, and the temperature of the glycerin is kept at 20°C ± 5°C for 15 minutes. Next, a steel ball is placed in the center of the surface of the sample in the ring, and this is placed in a fixed position on the holder. Next, keeping the distance from the top of the ring to the glycerin surface at 50 mm, place a thermometer and align the center of the thermometer's mercury bulb to the same height as the center of the ring, then heat the container. The flame of the Bunsen burner used for heating should be midway between the center of the bottom of the container and its edge, and heating should be uniform. After heating begins and the temperature of the bath reaches 40°C, the rate of increase must be 5.0 ± 0.5°C per minute. The sample gradually softens and flows down the ring, and the temperature is read when it finally touches the bottom plate, and this is the softening point. The softening point is measured for two or more samples at the same time, and the average value is used.

[0054] In the embodiment using the aromatic ring-containing tackifier resin, the proportion of the aromatic ring-containing tackifier resin is not particularly limited. In some preferred embodiments, the proportion of the aromatic ring-containing tackifier resin in the entire tackifier resin contained in the adhesive layer may be, for example, 30% by weight or more, 50% by weight or more (e.g., more than 50% by weight), 60% by weight or more, 70% by weight or more, or 75% by weight or more. By increasing the proportion of the aromatic ring-containing tackifier resin, the effect of containing the aromatic ring-containing tackifier resin (improvement of adhesive strength, cohesive strength, etc.) is easily obtained. In addition, in some preferred embodiments, the proportion of the aromatic ring-containing tackifier resin in the entire tackifier resin may be less than 100% by weight, for example, 90% by weight or less, 85% by weight or less, or 80% by weight or less. By appropriately limiting the proportion of the aromatic ring-containing tackifier resin, it is possible to achieve a good balance between adhesive strength and cohesive strength. This is also advantageous for improving repulsion resistance.

[0055] Although not particularly limited, when an aromatic ring-containing tackifier resin is used as the tackifier resin, in some embodiments, the content of the aromatic ring-containing tackifier resin relative to 100 parts by weight of the base polymer is 10 parts by weight or more, preferably 30 parts by weight or more, more preferably 40 parts by weight or more, even more preferably 50 parts by weight or more, and particularly preferably 60 parts by weight or more (for example, 65 parts by weight or more) from the viewpoint of cohesive strength. In some preferred embodiments, the content of the aromatic ring-containing tackifier resin relative to 100 parts by weight of the base polymer is, for example, 100 parts by weight or less, and from the viewpoint of adhesive strength and compatibility, it is more preferably 90 parts by weight or less, and may be 80 parts by weight or less.

[0056] In some embodiments, the tackifier resin contains a tackifier resin having an aromatic ring and a hydroxyl value of less than 40 mgKOH / g. Hereinafter, a tackifier resin having an aromatic ring and a hydroxyl value of less than 40 mgKOH / g may be referred to as "tackifier resin T1a". By using the tackifier resin T1a, it is possible to preferably achieve both improved adhesive strength and high cohesive strength based on a chemical structure containing an aromatic ring and a low hydroxyl value. In addition, although not particularly limited, the tackifier resin T1a has good compatibility with styrene-based block copolymers, can increase the cohesive strength of the styrene phase, and is likely to favorably exert its added effect on a styrene-based block copolymer-containing adhesive. The hydroxyl value of the tackifier resin T1a is preferably less than 30 mgKOH / g, more preferably less than 10 mgKOH / g, and may be less than 5 mgKOH / g or less than 3 mgKOH / g. In some embodiments, a tackifier resin T1a having a hydroxyl value of less than 1 mgKOH / g or no detectable hydroxyl groups may be preferably used. As the tackifier resin T1a, any of the aromatic ring-containing tackifier resins that satisfy the hydroxyl value described above may be used. Examples of preferred tackifier resins T1a include aromatic petroleum resins and styrene resins (e.g., α-methylstyrene / styrene copolymer resins). The tackifier resins T1a may be used alone or in combination of two or more.

[0057] In this specification, the hydroxyl value of the tackifier resin can be a value measured by potentiometric titration method as specified in JIS K0070: 1992. The specific measurement method is as follows. [Method for measuring hydroxyl value] 1. Reagents (1) As the acetylation reagent, take about 12.5 g (about 11.8 mL) of acetic anhydride, add pyridine to make the total volume 50 mL, and stir thoroughly before use. Alternatively, take about 25 g (about 23.5 mL) of acetic anhydride, add pyridine to make the total volume 100 mL, and stir thoroughly before use. (2) Use a 0.5 mol / L potassium hydroxide ethanol solution as the measurement reagent. (3) In addition, prepare toluene, pyridine, ethanol and distilled water. 2.Operation (1) Accurately weigh out approximately 2 g of sample into a flat-bottom flask, add 5 mL of acetylation reagent and 10 mL of pyridine, and attach an air condenser. (2) Heat the flask in a 100°C bath for 70 minutes, then allow it to cool, add 35 mL of toluene as a solvent from the top of the cooling tube and stir, then add 1 mL of distilled water and stir to decompose the acetic anhydride. Heat again in the bath for 10 minutes to complete the decomposition, then allow it to cool. (3) Wash the cooling tube with 5 mL of ethanol and remove it. Then, add 50 mL of pyridine as a solvent and stir. (4) Add 25 mL of 0.5 mol / L potassium hydroxide ethanol solution using a volumetric pipette. (5) Perform potentiometric titration with 0.5 mol / L potassium hydroxide ethanol solution. The inflection point of the obtained titration curve is the endpoint. (6) A blank test is carried out by carrying out steps (1) to (5) above without adding any sample. 3.Calculation The hydroxyl value is calculated according to the following formula. Hydroxyl value (mgKOH / g) = [(BC) x f x 28.05] / S + D Where: B: Amount (mL) of 0.5 mol / L potassium hydroxide ethanol solution used in the blank test. C: Amount of 0.5 mol / L potassium hydroxide ethanol solution used for the sample (mL), f: Factor of 0.5 mol / L potassium hydroxide ethanol solution, S: weight of sample (g), D: acid number, 28.05: 1 / 2 the molecular weight of potassium hydroxide, 56.11. It is.

[0058] In some embodiments, the tackifier resin contains a tackifier resin having an aromatic ring and substantially free of isoprene units, terpene skeletons, and rosin skeletons. Hereinafter, such a tackifier resin may be referred to as "tackifier resin T1b". Herein, the tackifier resin T1b substantially free of isoprene units, terpene skeletons, and rosin skeletons means that the proportion of these structural parts (i.e., isoprene units, terpene skeletons, and rosin skeletons) in the tackifier resin T1b is less than 10% by weight in total (more preferably less than 8% by weight, even more preferably less than 5% by weight, for example less than 3% by weight). The above proportion may be 0% by weight. The proportions of isoprene units, terpene skeletons, and rosin skeletons in the tackifier resin T1b can be measured, for example, by NMR (nuclear magnetic resonance spectroscopy). By using the tackifier resin T1b, it is possible to preferably achieve both improved adhesion and high cohesive strength based on the above chemical structure containing an aromatic ring. In addition, although not particularly limited, the tackifier resin T1b has good compatibility with styrene-based block copolymers, can increase the cohesive force of the styrene phase, and is easy to favorably exhibit its added effect on styrene-based block copolymer-containing adhesives. Examples of the tackifier resin T1b include the above-mentioned aromatic petroleum resins, aliphatic / aromatic copolymer petroleum resins, styrene-based resins, coumarone-indene resins, etc. Among them, aromatic petroleum resins and styrene-based resins (e.g., α-methylstyrene / styrene copolymer resins) are preferred as the tackifier resin T1b. The tackifier resin T1b can be used alone or in combination of two or more kinds. As the tackifier resin T1b, one that also corresponds to the tackifier resin T1a can be preferably used. Similarly, as the tackifier resin T1a, one that also corresponds to the tackifier resin T1b can be preferably used.

[0059] In some preferred embodiments, the adhesive layer contains an aromatic petroleum resin as a tackifier resin. Aromatic petroleum resins are also called C9 petroleum resins. Hereinafter, aromatic petroleum resins may be referred to as "aromatic petroleum resin T1c". By using aromatic petroleum resins, it is possible to preferably achieve both improved adhesive strength and high cohesive strength based on a chemical structure containing an aromatic ring. In addition, although not particularly limited, aromatic petroleum resins have good compatibility with styrene block copolymers, can increase the cohesive strength of the styrene phase, and are likely to exhibit the effects of adding them to styrene block copolymer-containing adhesives. The aromatic petroleum resins can be used alone or in combination of two or more.

[0060] Although not particularly limited, aromatic petroleum resins having a hydroxyl value of less than 40 mgKOH / g may be preferably used. The hydroxyl value of the aromatic petroleum resin is preferably less than 30 mgKOH / g, more preferably less than 10 mgKOH / g, and may be less than 5 mgKOH / g or less than 3 mgKOH / g. In some embodiments, aromatic petroleum resins having a hydroxyl value of less than 1 mgKOH / g or having no detectable hydroxyl groups may be preferably used.

[0061] The above-mentioned tackifier resins T1a, T1b, and aromatic petroleum resin T1c may be collectively referred to as "tackifier resin T1". In this specification, tackifier resin T1 is defined as a concept that includes tackifier resins T1a, T1b, and aromatic petroleum resin T1c. Therefore, unless otherwise specified, the technical matters described for tackifier resin T1 can be applied to tackifier resins T1a, T1b, and aromatic petroleum resin T1c, respectively.

[0062] Although not particularly limited, the softening point of the tackifier resin T1 is preferably higher than 100° C. From the viewpoint of improving the cohesive strength (e.g., high-temperature cohesive strength) and improving the repulsion resistance, a tackifier resin T1 having a softening point of 120° C. or higher can be preferably used. The tackifier resin T1 having a softening point of 120° C. or higher is the tackifier resin T described below.H In some embodiments, the softening point of the tackifier resin T1 is more preferably 130° C. or higher, further preferably 135° C. or higher, particularly preferably 140° C. or higher, and may be 150° C. or higher (e.g., more than 150° C.). From the viewpoint of adhesive strength, the softening point of the tackifier resin T1 is usually 200° C. or lower, preferably 180° C. or lower, and more preferably 170° C. or lower (e.g., 160° C. or lower).

[0063] In the embodiment in which the tackifier resin T1 is used, the proportion of the tackifier resin T1 used is not particularly limited. In some preferred embodiments, the proportion of the tackifier resin T1 in the total tackifier resin contained in the adhesive layer may be, for example, 5% by weight or more, 10% by weight or more, 15% by weight or more, 20% by weight or more, 25% by weight or more, or 30% by weight or more. By increasing the proportion of the tackifier resin T1 used, the effect of adding the tackifier resin (improvement of adhesive strength, cohesive strength, etc.) is easily obtained. In addition, in some preferred embodiments, the proportion of the tackifier resin T1 in the total tackifier resin may be 70% by weight or less, 60% by weight or less, 50% by weight or less (for example, less than 50% by weight), or 40% by weight or less. By appropriately limiting the proportion of the tackifier resin T1 used, it is possible to achieve a good balance between adhesive strength and cohesive strength. This is also advantageous for improving repulsion resistance.

[0064] Although not particularly limited, in some embodiments, the content of the tackifier resin T1 relative to 100 parts by weight of the base polymer is about 1 part by weight or more, and may be 5 parts by weight or more. In some preferred embodiments, the content of the tackifier resin T1 relative to 100 parts by weight of the base polymer is 10 parts by weight or more, more preferably 15 parts by weight or more, even more preferably 20 parts by weight or more, and may be 25 parts by weight or more. By increasing the amount of the tackifier resin T1, the effect of adding it (improvement of adhesive strength and cohesive strength, etc.) is easily obtained. In addition, in some preferred embodiments, the content of the tackifier resin T1 relative to 100 parts by weight of the base polymer is, for example, 70 parts by weight or less, more preferably 50 parts by weight or less, even more preferably 40 parts by weight or less, and may be 35 parts by weight or less, from the viewpoint of compatibility, etc. By appropriately limiting the amount of the tackifier resin T1, it is possible to achieve a good balance between adhesive strength and cohesive strength.

[0065] In some embodiments, the adhesive layer contains one or more terpene phenol resins. Hereinafter, the terpene phenol resin may be referred to as "terpene phenol resin T2". By using an adhesive containing a terpene phenol resin, a higher performance adhesive sheet can be realized. For example, an adhesive sheet that has both adhesive strength and cohesive strength at a higher level can be realized.

[0066] Although not particularly limited, the softening point of the terpene phenol resin is preferably higher than 100° C. From the viewpoint of improving cohesive strength (e.g., high-temperature cohesive strength) and repulsion resistance, a terpene phenol resin having a softening point of 120° C. or higher can be preferably used. The terpene phenol resin having a softening point of 120° C. or higher is preferably used as the tackifier resin T described later. HIn some embodiments, the softening point of the terpene phenol resin is more preferably 125° C. or higher, even more preferably 130° C. or higher, particularly preferably 135° C. or higher, and may be 140° C. or higher. From the viewpoint of adhesive strength, the softening point of the terpene phenol resin is usually 200° C. or lower, preferably 180° C. or lower, more preferably 170° C. or lower, even more preferably 160° C. or lower, and particularly preferably 150° C. or lower.

[0067] When a terpene phenol resin is used as a tackifier resin, in some preferred embodiments, from the viewpoint of adhesive properties such as improved adhesive strength, the proportion of the terpene phenol resin in the total amount of the tackifier resin is, for example, 15% by weight or more, more preferably 25% by weight or more, even more preferably 30% by weight or more, particularly preferably 35% by weight or more, and may be 40% by weight or more. In some embodiments, the proportion of the terpene phenol resin in the total amount of the tackifier resin may be, for example, 90% by weight or less, preferably 80% by weight or less, 70% by weight or less, 60% by weight or less, or 50% by weight or less. By limiting the amount of the terpene phenol resin used, the stability over time of the adhesive layer tends to be improved.

[0068] When the pressure-sensitive adhesive layer contains a terpene phenol resin as a tackifier resin, the content of the terpene phenol resin is not particularly limited, and in some embodiments, from the viewpoint of adhesive properties such as improved adhesive strength, the content is appropriately 5 parts by weight or more relative to 100 parts by weight of the base polymer, preferably 10 parts by weight or more (e.g., more than 10 parts by weight), more preferably 20 parts by weight or more, even more preferably 30 parts by weight or more, and may be 35 parts by weight or more. In some embodiments, from the viewpoint of stability over time, the content of the terpene phenol resin in the pressure-sensitive adhesive layer is appropriately 70 parts by weight or less relative to 100 parts by weight of the base polymer, preferably 60 parts by weight or less, more preferably 50 parts by weight or less, and may be 45 parts by weight or less.

[0069] Although not particularly limited, a terpene phenol resin having a hydroxyl value of 80 mgKOH / g or more (e.g., 90 mgKOH / g or more) is preferably used as the terpene phenol resin T2. ​​Hereinafter, a terpene phenol resin having a hydroxyl value of 80 mgKOH / g or more (e.g., 90 mgKOH / g or more) may be referred to as a "terpene phenol resin T2a". The hydroxyl value of the terpene phenol resin T2a is typically 200 mgKOH / g or less, preferably 180 mgKOH / g or less, for example, 160 mgKOH / g or less. A pressure-sensitive adhesive sheet with higher performance can be realized by using a pressure-sensitive adhesive containing the terpene phenol resin T2a. For example, a pressure-sensitive adhesive sheet that achieves both adhesive strength and cohesive strength at a higher level can be realized.

[0070] In the embodiment in which the terpene phenol resin T2a is used as the tackifier resin, the ratio of the terpene phenol resin T2a in the entire terpene phenol resin is not particularly limited. In some embodiments, from the viewpoint of effectively obtaining the effect of the terpene phenol resin T2a blending, the ratio of the terpene phenol resin T2a in the entire terpene phenol resin T2 is, for example, 10% by weight or more, may be 20% by weight or more, may be 30% by weight or more, or may be 40% by weight or more. In some embodiments, the ratio may be, for example, 90% by weight or less, may be 80% by weight or less, may be 70% by weight or less, or may be 60% by weight or less.

[0071] Although not particularly limited, a terpene phenol resin having a hydroxyl value of 40 mgKOH / g or more and less than 80 mgKOH / g is preferably used as the terpene phenol resin. Hereinafter, a terpene phenol resin having a hydroxyl value of 40 mgKOH / g or more and less than 80 mgKOH / g may be referred to as "terpene phenol resin T2b". The hydroxyl value of the terpene phenol resin T2b may be 45 mgKOH / g or more, or 50 mgKOH / g or more. In addition, the hydroxyl value of the terpene phenol resin T2b may be 75 mgKOH / g or less, or 70 mgKOH / g or less.

[0072] In the embodiment in which the terpene phenol resin T2b is used as the tackifier resin, the ratio of the terpene phenol resin T2b in the entire terpene phenol resin T2 is not particularly limited. In some embodiments, from the viewpoint of effectively obtaining the effect of the incorporation of the terpene phenol resin T2b, the ratio of the terpene phenol resin T2b in the entire terpene phenol resin T2 is, for example, 10% by weight or more, may be 20% by weight or more, may be 30% by weight or more, or may be 40% by weight or more. In some embodiments, the ratio may be, for example, 90% by weight or less, may be 80% by weight or less, may be 70% by weight or less, or may be 60% by weight or less.

[0073] In some preferred embodiments, the terpene phenol resin T2a and the terpene phenol resin T2b can be used in combination. In such embodiments, the relationship between the amounts of T2a and T2b used can be set, for example, so that the weight ratio (T2a / T2b) is in the range of 1 / 5 to 5 / 1. From the viewpoint of effectively obtaining the effect of using the terpene phenol resin T2a, the weight ratio (T2a / T2b) is preferably 1 / 3 or more, more preferably 1 / 2 or more, even more preferably 2 / 3 or more, and may be 5 / 6 or more. From the viewpoint of effectively obtaining the effect of using the terpene phenol resin T2b, the weight ratio (T2a / T2b) is preferably 3 or less, more preferably 2 or less, even more preferably 3 / 2 or less, and may be 6 / 5 or less. By using the terpene phenol resins T2a and T2b having different hydroxyl values ​​in combination, a pressure-sensitive adhesive having a good balance between adhesive strength and cohesive strength and excellent repulsion resistance can be preferably designed.

[0074] In some embodiments, it is preferable to use the above-mentioned tackifier resin T1 and terpene phenol resin T2 in combination. By using the tackifier resin T1 and the terpene phenol resin T2 in combination, it is possible to design a pressure-sensitive adhesive having better adhesive properties (adhesive strength, cohesive strength, and even repulsion resistance, etc.). In such an embodiment, the relationship between the amount of the tackifier resin T1 and the terpene phenol resin T2 used is not particularly limited, and the weight ratio (T1 / T2) is, for example, 0.1 or more, and from the viewpoint of effectively obtaining the effect of using the tackifier resin T1, is preferably 0.3 or more, more preferably 0.5 or more, and even more preferably 0.7 or more. In some preferred embodiments, the weight ratio (T1 / T2) is preferably 10 or less, more preferably 5 or less, even more preferably 3 or less, and particularly preferably 2 or less, and may be 1.0 or less (for example, less than 1.0) from the viewpoint of effectively obtaining the effect of using the terpene phenol resin T2.

[0075] In some embodiments, the adhesive layer contains a terpene resin as a tackifier resin. Hereinafter, such a tackifier resin may be referred to as "tackifier resin T3". The terpene resin referred to here is typically a non-modified terpene resin and does not contain an aromatic ring. The softening point of the terpene resin is not particularly limited, and for example, from the viewpoint of improving adhesive strength, a terpene resin having a softening point of less than 120°C is preferably used. The lower limit of the softening point of the terpene resin is not particularly limited. Usually, a terpene resin having a softening point of 40°C or more (typically 60°C or more) can be preferably used. From the viewpoint of achieving both adhesive strength and cohesive strength at a high level, usually, a terpene resin having a softening point of 80°C or more (more preferably 100°C or more) and less than 120°C can be preferably used. Among them, the use of a terpene resin having a softening point of 110°C or more and less than 120°C is preferred.

[0076] In the embodiment in which the terpene resin is used as the tackifier resin, the proportion of the terpene resin is not particularly limited. In some preferred embodiments, the proportion of the terpene resin in the total tackifier resin contained in the adhesive layer is, for example, 1% by weight or more, more preferably 5% by weight or more, even more preferably 10% by weight or more, particularly preferably 15% by weight or more, and may be 20% by weight or more. In some preferred embodiments, the proportion of the terpene resin in the total tackifier resin is 50% by weight or less, more preferably 40% by weight or less, even more preferably 30% by weight or less, and may be 25% by weight or less. By using the terpene resin in the above range of proportion, it is possible to preferably achieve both adhesive strength and cohesive strength.

[0077] Although not particularly limited, when using a terpene resin as a tackifier resin, in some embodiments, the content of the terpene resin relative to 100 parts by weight of base polymer is about 1 part by weight or more, and may be 5 parts by weight or more, from the viewpoint of improving adhesion.In some preferred embodiments, the content of the terpene resin relative to 100 parts by weight of base polymer is 10 parts by weight or more, more preferably 15 parts by weight or more, and may be 18 parts by weight or more.In some preferred embodiments, the content of the terpene resin relative to 100 parts by weight of base polymer is, for example, 50 parts by weight or less, and from the viewpoint of cohesive strength and compatibility, it is more preferably 40 parts by weight or less, more preferably 30 parts by weight or less, and may be 25 parts by weight or less.

[0078] In some embodiments, it is preferable to use at least one selected from the above-mentioned tackifier resin T1 and terpene phenol resin T2 in combination with terpene resin T3. By using the tackifier resin T1 or the terpene phenol resin T2 in combination with terpene resin T3, it is possible to preferably design a pressure-sensitive adhesive that achieves both adhesive strength and cohesive strength at a higher level. In particular, it is more preferable to use the tackifier resin T1 in combination with terpene phenol resin T2 and terpene resin T3 as the tackifier resin.

[0079] In some embodiments, the adhesive layer is a tackifier resin having a softening point of 120° C. or higher (hereinafter, “tackifier resin T H It is preferable that the adhesive contains a tackifier resin having a high softening point. By using a tackifier resin having a high softening point, it is possible to improve the heat resistance stability of the adhesive properties. From the viewpoint of repulsion resistance and high temperature cohesive strength, it is preferable that the tackifier resin contains a tackifier resin having a high softening point. H The softening point of the tackifier resin T is preferably 125° C. or higher, more preferably 130° C. or higher, and even more preferably 135° C. or higher (e.g., 140° C. or higher). H The softening point of the resin is usually 200° C. or lower, preferably 180° C. or lower, and more preferably 170° C. or lower (eg, 160° C. or lower).

[0080] Tackifying resin T H As the resin, one or more of the above-mentioned petroleum resins, styrene-based resins, coumarone-indene resins, modified terpene resins, rosin-based resins, rosin derivative resins, ketone-based resins, etc. can be used. Among them, aromatic petroleum resins, terpene phenol resins, rosin phenol resins, polymerized rosin, and esterified products of polymerized rosin are preferred, and aromatic petroleum resins and terpene phenol resins are more preferred.

[0081] Although not particularly limited, tackifier resin T H When using tackifier resin T H From the viewpoint of cohesive strength, the total amount of tackifier resin T (i.e., the total amount of tackifier resins having a softening point of 120° C. or more) is suitably 10 parts by weight or more, preferably 30 parts by weight or more, more preferably 40 parts by weight or more, even more preferably 50 parts by weight or more, and particularly preferably 60 parts by weight or more (e.g., 65 parts by weight or more). H The content can be, for example, 100 parts by weight or less, and from the viewpoint of adhesive strength and compatibility, it is appropriate to make it 90 parts by weight or less, and preferably 80 parts by weight or less.

[0082] Although not particularly limited, tackifier resin T H When using tackifier resin T, the proportion of tackifier resin T in the total amount of tackifier resin H From the viewpoint of cohesive strength, the proportion is suitably about 20% by weight or more, and in some preferred embodiments, it is 30% by weight or more, more preferably 50% by weight or more (e.g., more than 50% by weight), even more preferably 60% by weight or more, particularly preferably 70% by weight or more, and may be 75% by weight or more. In some embodiments, the proportion is preferably, for example, 95% by weight or less, and from the viewpoint of improving adhesive strength, it is more preferably 90% by weight or less, and even more preferably 85% by weight or less, and may be 80% by weight or less.

[0083] In some embodiments, the tackifier resin is a tackifier resin having a softening point of less than 120° C. (hereinafter, “tackifier resin T L It is preferable that the tackifier resin T L By using the tackifier resin T, a pressure-sensitive adhesive sheet having excellent adhesive strength can be preferably realized. L is the above-mentioned tackifier resin T H It is preferable to use it in combination with Tackifier Resin T. H and tackifier resin T L By using these in combination, it is possible to obtain a good balance between adhesive strength and cohesive strength, thereby making it possible to suitably realize a PSA sheet having excellent repulsion resistance.

[0084] Tackifying resin T L The lower limit of the softening point of the tackifier resin T is not particularly limited. Usually, a softening point of 40° C. or higher (typically 60° C. or higher) can be preferably used. From the viewpoint of achieving both high levels of adhesive strength and cohesive strength, usually, a softening point of 80° C. or higher (more preferably 100° C. or higher) and less than 120° C. can be used. L Among them, tackifier resin T having a softening point of 110° C. or more and less than 120° C. is preferably used. L The use of is preferred.

[0085] Tackifying resin T L As the tackifier resin, those having a softening point of less than 120°C among the various types of tackifier resins mentioned above (petroleum resins, styrene-based resins, coumarone-indene resins, terpene resins, modified terpene resins, rosin-based resins, rosin derivative resins, ketone-based resins, etc.) can be used alone or in appropriate combination.

[0086] The technology disclosed herein is a method for producing the adhesive comprising the steps of: L For example, the tackifier resin T L The main component of (i.e., tackifier resin T L In terms of adhesion and compatibility, the tackifier resin T may preferably be a petroleum resin, a terpene resin, or a combination of a petroleum resin and a terpene resin. L A preferred embodiment is one in which the main component of the tackifier resin T is a terpene resin (e.g., a β-pinene polymer). L Substantially all (for example, 95% by weight or more) of the resin may be a terpene resin.

[0087] Tackifying resin T L When using tackifier resin T L From the viewpoint of cohesive strength, the total amount of tackifier resin T (i.e., the total amount of tackifier resins having a softening point of less than 120° C.) is, in some embodiments, suitably 50 parts by weight or less, preferably 40 parts by weight or less, more preferably 35 parts by weight or less, even more preferably 30 parts by weight or less, and may be 25 parts by weight or less. L The content may be, for example, 5 parts by weight or more, and from the viewpoint of improving adhesion and impregnation into the fibrous base material, it is preferably 10 parts by weight or more, more preferably 15 parts by weight or more, and even more preferably 20 parts by weight or more.

[0088] In some embodiments, the tackifier resin T L and tackifier resin T HIt is preferable to use in combination with Tackifier Resin T. L and tackifier resin T H By using the tackifier resin T in combination, it is possible to preferably design a PSA that has both high levels of adhesive strength and high cohesive strength, and it is possible to preferably achieve even better repulsion resistance. L and tackifier resin T H The relationship between the amount of use and the weight ratio (T L / T H ) is, for example, 0.05 or more, and the tackifier resin T L From the viewpoint of effectively obtaining the effect of use, the weight ratio (T L / T H ) is tackifier resin T H From the viewpoint of effectively obtaining the effect of use, it is preferably 3 or less, more preferably 1.0 or less, further preferably 0.50 or less, particularly preferably 0.40 or less, and may be 0.35 or less.

[0089] When the adhesive layer contains a tackifier resin, the total amount of the tackifier resin is not particularly limited. In some embodiments, the total amount of the tackifier resin relative to 100 parts by weight of the base polymer is usually 10 parts by weight or more, preferably 30 parts by weight or more, more preferably 50 parts by weight or more (e.g., more than 50 parts by weight), even more preferably 70 parts by weight or more, particularly preferably 80 parts by weight or more, and may be 85 parts by weight or more. In some embodiments, the total amount of the tackifier resin relative to 100 parts by weight of the base polymer is usually 200 parts by weight or less, preferably 150 parts by weight or less, more preferably 120 parts by weight or less, and even more preferably 100 parts by weight or less (e.g., less than 100 parts by weight). By setting the amount of the tackifier resin to be used within the above range, a pressure-sensitive adhesive that has a good balance between adhesive strength and cohesive strength can be preferably designed, and excellent repulsion resistance can be preferably realized.

[0090] (Black pigment) The adhesive layer typically contains a black pigment, which allows the desired L * It is possible to obtain a pressure-sensitive adhesive layer having the following characteristics. Specific examples of black pigments include carbon black, graphite, aniline black, perylene black, titanium black, cyanine black, etc. The black pigments can be used alone or in appropriate combination of two or more.

[0091] In some preferred embodiments, the adhesive layer contains carbon black particles. As the carbon black particles to be used, those generally called carbon black (furnace black, channel black, acetylene black, thermal black, lamp black, pine soot, etc.) can be used without any particular limitation. In addition, as the carbon black particles, surface-modified carbon black particles having functional groups such as carboxyl groups, amino groups, sulfonic acid groups, and silicon-containing groups (e.g., alkoxysilyl groups, alkylsilyl groups) can also be used. Such surface-modified carbon black particles are also called self-dispersing carbon black, and can reduce the amount of dispersant added. The above carbon black particles can be used alone or in combination of two or more types.

[0092] By using a small amount * From the viewpoint of efficiently reducing the above, in some preferred embodiments, a black pigment (preferably carbon black particles) having an average particle diameter of about 10 nm or more (e.g., about 30 nm or more) can be used. The above average particle diameter is, for example, about 50 nm or more, and may be about 100 nm or more, or may be about 150 nm or more. Black pigments having the above average particle diameter tend to have good dispersion stability in the adhesive layer, and are less likely to undergo intralayer movement such as bleed-out. There is no particular upper limit to the average particle diameter of the black pigment, and is, for example, appropriately about 3000 nm or less, and may be about 1500 nm or less (e.g., 1200 nm or less). L *From the viewpoint of reduction, the average particle size of the black pigment is preferably less than 1000 nm, more preferably less than 500 nm, and even more preferably less than 300 nm, and may be less than 250 nm (e.g., less than about 220 nm). A black pigment having an average particle size in the above range tends to disperse well in the pressure-sensitive adhesive layer with a relatively small amount added, and to easily obtain a high degree of blackness.

[0093] In this specification, the average particle size of the black pigment (preferably carbon black particles) refers to the volume average particle size, and specifically refers to the particle size at 50% of the cumulative value in the particle size distribution measured using a particle size distribution measuring device based on the laser scattering and diffraction method (50% volume average particle size; hereinafter, D 50 As a measuring device, for example, a product named "Microtrac MT3000II" manufactured by Microtrac Bell or an equivalent product can be used.

[0094] The content of the black pigment (preferably carbon black particles) in the adhesive layer is not particularly limited, and may be determined according to the thickness of the adhesive layer and the L * , may be appropriately set in consideration of the required adhesive properties, etc. In some embodiments, the content of the black pigment in the adhesive layer is, for example, about 0.1% by weight or more, and from the viewpoint of improving the blackness, it is preferably about 0.5% by weight or more, more preferably about 0.7% by weight or more, and even more preferably 0.8% by weight or more. In some embodiments, from the viewpoint of adhesive properties, etc., the content of the black pigment is, for example, about 10% by weight or less, and may be about 5.0% by weight or less, or may be about 3.0% by weight or less. In some preferred embodiments, from the viewpoint of obtaining excellent repulsion resistance, the content of the black pigment is about 2.0% by weight or less, more preferably about 1.6% by weight or less, may be about 1.2% by weight or less, may be about 1.0% by weight or less (for example, less than 1.0% by weight), may be about 0.9% by weight or less, may be 0.8% by weight or less, or may be 0.7% by weight or less.

[0095] In some embodiments, the black pigment is preferably blended in the pressure-sensitive adhesive layer in the form of a dispersion containing the black pigment. By blending a dispersion in which at least a portion of the black pigment is dispersed in a pressure-sensitive adhesive composition to form a pressure-sensitive adhesive layer, L * The black pigment dispersion is preferably used in the form of a dispersion liquid that is liquid at room temperature (for example, 23° C.).

[0096] The black pigment dispersion preferably contains a component that contributes to improving the dispersibility of the black pigment. Such a component may be, for example, a polymer, an oligomer, a liquid resin, a surfactant, or the like. The above components may be used alone or in combination of two or more. The oligomer may be, for example, a polymer having a Mw of about 10×10 4 Less than 5 x 10 4 Examples of the liquid resin include acrylic oligomers having a molecular weight of less than 10000000. The liquid resin is a resin that is liquid at 30° C., and examples of the liquid resin include rosin compounds, terpene compounds, and hydrocarbon compounds. The surfactant may be any of anionic, cationic, nonionic, and amphoteric surfactants.

[0097] In some preferred embodiments, the black pigment dispersion contains a black pigment and a liquid resin. In the dispersion, at least a part of the black pigment is dispersed in the liquid resin. By using a dispersion having the above configuration, a high degree of blackness is easily obtained. In addition, in an embodiment using a black pigment dispersion containing a black pigment and a liquid resin, the effect of the technology disclosed herein (specifically, high blackness and repulsion resistance) can be preferably realized by designing the adhesive to have the above-mentioned SS breaking strength characteristics. Although not particularly limited, in some embodiments, a liquid resin having a viscosity at 25°C of, for example, about 30000 mPa·s or less is used. The viscosity may be about 20000 mPa·s or less, or about 10000 mPa·s or less. In some embodiments, the viscosity of the liquid resin at 25°C may be, for example, about 1000 mPa·s or more, or about 3000 mPa·s or more. In this specification, the viscosity of a liquid resin at 25°C refers to the viscosity measured under conditions of 25°C ± 5°C, and can be measured using a commercially available viscometer or rheometer.

[0098] As described above, the liquid resin may be included in the adhesive layer together with the black pigment in the formulation of the black pigment dispersion. In such an embodiment, the liquid resin is included in the adhesive layer within a range that satisfies the above-mentioned SS breaking strength characteristics. Although not particularly limited, in some embodiments, the content of the liquid resin in the adhesive layer may be about 9.5 parts by weight or less, or about 8.0 parts by weight or less per 100 parts by weight of the base polymer contained in the adhesive layer. In some preferred embodiments, the content of the liquid resin is, for example, about 6.5 parts by weight or less, more preferably about 5.0 parts by weight or less, even more preferably about 4.0 parts by weight or less, and may be about 3.5 parts by weight or less, or may be about 3.0 parts by weight or less per 100 parts by weight of the base polymer contained in the adhesive layer. By limiting the amount of the liquid resin contained in the black pigment dispersion as described above, it is easy to maintain repulsion resistance. In addition, in some preferred embodiments, the content of the liquid resin may be approximately 1 part by weight or more, approximately 1.5 parts by weight or more, approximately 2.0 parts by weight or more, approximately 3.0 parts by weight or more, approximately 4.0 parts by weight or more, or approximately 5.0 parts by weight or more per 100 parts by weight of the base polymer contained in the adhesive layer, taking into consideration, for example, the dispersibility of the above-mentioned black pigment in the adhesive layer.

[0099] Although not particularly limited, in some embodiments, the content of the liquid resin in the adhesive layer is, for example, suitably about 4.5% by weight or less, may be about 4.0% by weight or less, or may be about 3.5% by weight or less. In some preferred embodiments, the content of the liquid resin in the adhesive layer is about 3.3% by weight or less, more preferably about 3.0% by weight or less, even more preferably about 2.5% by weight or less, particularly preferably about 2.0% by weight or less, and may be, for example, 1.5% by weight or less. By limiting the amount of the liquid resin contained in the black pigment dispersion as described above, it is easy to adjust the SS breaking strength property within a specific range, and the repulsion resistance can be preferably improved. In addition, in some embodiments, the content of the liquid resin may be, for example, approximately 0.1% by weight or more, approximately 0.5% by weight or more, approximately 1.0% by weight or more, approximately 1.5% by weight or more, or approximately 2.0% by weight or more, taking into consideration, for example, the dispersibility of the black pigment described above in the adhesive layer.

[0100] In an embodiment in which the black pigment is blended in the PSA in the form of a dispersion, the black pigment dispersion may contain water (ion-exchanged water, reverse osmosis water, distilled water, etc.), various organic solvents (alcohols such as ethanol, etc.; ketones such as acetone, etc.; ethers such as butyl cellosolve and propylene glycol monomethyl ether acetate, etc.; esters such as ethyl acetate, etc.; aromatic hydrocarbons such as toluene, etc.; and mixed solvents thereof), an aqueous mixed solvent of water and the above-mentioned organic solvents, and other additives.

[0101] In the embodiment in which the black pigment is blended in the adhesive in the form of a dispersion, the amount of the black pigment contained in the black pigment dispersion is not particularly limited. In some embodiments, the amount of the black pigment contained in the black pigment dispersion may be about 1% by weight or more, and from the viewpoint of efficient improvement of blackness, it is appropriate to make it, for example, about 10% by weight or more, preferably about 15% by weight or more, more preferably about 20% by weight or more, and even more preferably about 25% by weight or more. In some embodiments, from the viewpoint of improving the dispersibility of the black pigment in the adhesive layer, it is appropriate to make the amount of the black pigment in the dispersion, for example, about 70% by weight or less, preferably about 50% by weight or less (for example, less than 50% by weight), more preferably about 40% by weight or less, and even more preferably about 35% by weight or less.

[0102] In the black pigment dispersion containing a black pigment and a liquid resin, the content of the liquid resin contained in the dispersion is, in some preferred embodiments, from the viewpoint of dispersing the black pigment more uniformly in the adhesive layer, 1 time or more of the content of the black pigment, more preferably about 1.2 times or more, even more preferably about 1.5 times or more, particularly preferably about 1.8 times or more, and may be about 2.0 times or more. In addition, in some embodiments, from the viewpoint of efficiently increasing the blackness, the content of the liquid resin contained in the dispersion is about 10 times or less of the content of the black pigment, preferably about 5 times or less, more preferably about 3 times or less, and even more preferably about 2.5 times or less. Although not particularly limited, in some embodiments, the content of the liquid resin in the black pigment dispersion is suitably about 30% by weight or more, preferably about 50% by weight or more (for example, more than 50% by weight), more preferably about 55% by weight or more, and even more preferably about 60% by weight or more. In some embodiments, the content of the liquid resin in the black pigment dispersion is suitably about 90% by weight or less, preferably about 80% by weight or less, more preferably about 75% by weight or less, and even more preferably about 70% by weight or less.

[0103] The black pigment and its dispersion can be prepared by mixing the above-mentioned carbon black, liquid resin, other dispersants, etc., or a commercially available product obtained from a manufacturer such as Toyo Color Co., Ltd. or Dainichi Seika Color & Chemicals Mfg. Co., Ltd. may be used by appropriately adjusting the composition.

[0104] In an embodiment in which the black pigment is blended in the form of a dispersion into the PSA, the blending amount of the black pigment dispersion is set to the desired blackness (L * ) and SS breaking strength after storage at high temperature and high humidity, and is not limited to a specific range. In some preferred embodiments, the blending amount of the black pigment dispersion is about 4 parts by weight or more, or may be about 5 parts by weight or more, or may be about 6 parts by weight or more, or may be about 8 parts by weight or more, based on the non-volatile content, per 100 parts by weight of the base polymer contained in the pressure-sensitive adhesive layer. Thereby, L * It is preferable to form a pressure-sensitive adhesive layer having a value of 10 or less. In some embodiments, the blending amount of the black pigment dispersion may be, for example, about 14 parts by weight or less, or about 12 parts by weight or less, per 100 parts by weight of the base polymer contained in the pressure-sensitive adhesive layer, based on the non-volatile content. In some preferred embodiments, the blending amount of the black pigment dispersion is, for example, about 10 parts by weight or less, or about 8 parts by weight or less, or about 6 parts by weight or less, per 100 parts by weight of the base polymer contained in the pressure-sensitive adhesive layer, based on the non-volatile content. By limiting the amount of the black pigment dispersion used as described above, it is easy to adjust the SS breaking strength property within a specific range, and the repulsion resistance can be preferably maintained.

[0105] (Isocyanate compounds) The adhesive composition disclosed herein may further contain an isocyanate compound. The isocyanate compound improves the cohesive strength of the adhesive and may be useful in realizing an adhesive sheet exhibiting higher adhesive strength. As the isocyanate compound, a polyfunctional isocyanate (meaning a compound having an average of two or more isocyanate groups per molecule, including those having an isocyanurate structure) may be preferably used. As such a polyfunctional isocyanate, one or more selected from various isocyanate compounds (polyisocyanates) having two or more isocyanate groups per molecule may be used. Examples of such a polyfunctional isocyanate include aliphatic polyisocyanates, alicyclic polyisocyanates, aromatic polyisocyanates, and the like.

[0106] Specific examples of aliphatic polyisocyanates include 1,2-ethylene diisocyanate; tetramethylene diisocyanates such as 1,2-tetramethylene diisocyanate, 1,3-tetramethylene diisocyanate, and 1,4-tetramethylene diisocyanate; hexamethylene diisocyanates such as 1,2-hexamethylene diisocyanate, 1,3-hexamethylene diisocyanate, 1,4-hexamethylene diisocyanate, 1,5-hexamethylene diisocyanate, 1,6-hexamethylene diisocyanate, and 2,5-hexamethylene diisocyanate; 2-methyl-1,5-pentane diisocyanate, 3-methyl-1,5-pentane diisocyanate, and lysine diisocyanate.

[0107] Specific examples of alicyclic polyisocyanates include isophorone diisocyanate; cyclohexyl diisocyanates such as 1,2-cyclohexyl diisocyanate, 1,3-cyclohexyl diisocyanate, and 1,4-cyclohexyl diisocyanate; cyclopentyl diisocyanates such as 1,2-cyclopentyl diisocyanate and 1,3-cyclopentyl diisocyanate; hydrogenated xylylene diisocyanate, hydrogenated tolylene diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated tetramethylxylene diisocyanate, and 4,4'-dicyclohexylmethane diisocyanate.

[0108] Specific examples of aromatic polyisocyanates include 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate, 4,4'-diphenylether diisocyanate, 2-nitrodiphenyl-4,4'-diisocyanate, 2,2'-diphenylpropane-4,4'-diisocyanate, Examples of the diisocyanate include 3,3'-dimethyldiphenylmethane-4,4'-diisocyanate, 4,4'-diphenylpropane diisocyanate, m-phenylene diisocyanate, p-phenylene diisocyanate, naphthylene-1,4-diisocyanate, naphthylene-1,5-diisocyanate, 3,3'-dimethoxydiphenyl-4,4'-diisocyanate, xylylene-1,4-diisocyanate, and xylylene-1,3-diisocyanate.

[0109] A preferred example of the isocyanate compound is a polyfunctional isocyanate having an average of three or more isocyanate groups per molecule. Such a trifunctional or higher isocyanate may be a multimer (typically a dimer or trimer) of a bifunctional or trifunctional or higher isocyanate, a derivative (for example, an addition reaction product of a polyhydric alcohol and two or more molecules of a polyfunctional isocyanate), a polymer, etc. For example, a dimer or trimer of diphenylmethane diisocyanate, an isocyanurate of hexamethylene diisocyanate (a trimer adduct of an isocyanurate structure), a reaction product of trimethylolpropane and tolylene diisocyanate, a reaction product of trimethylolpropane and hexamethylene diisocyanate, polymethylene polyphenyl isocyanate, polyether polyisocyanate, polyester polyisocyanate, and other polyfunctional isocyanates may be mentioned.

[0110] When an isocyanate compound is used, its amount is not particularly limited, but can be, for example, more than 0 part by weight and 10 parts by weight or less (typically 0.01 to 10 parts by weight) relative to 100 parts by weight of the base polymer. Usually, it is appropriate to use an isocyanate compound in an amount of 0.1 to 10 parts by weight relative to 100 parts by weight of the base polymer, and it is preferably 0.1 to 5 parts by weight (typically 0.3 to 3 parts by weight, for example 0.5 to 1 part by weight). By using an isocyanate compound in such a range, a pressure-sensitive adhesive sheet with particularly excellent balance of performance can be realized.

[0111] (Anti-aging agent) In some embodiments, it is preferable that the adhesive layer contains an antioxidant. The use of the antioxidant can suppress the deterioration of the adhesive due to storage, etc., and improve the stability of the adhesive over time. The antioxidant may be used alone or in combination of two or more. Examples of the antioxidant include phosphorus-based antioxidants, phenol-based antioxidants (hindered phenol-based antioxidants, etc.), hindered amine-based antioxidants, aromatic amine-based antioxidants, and sulfur-based antioxidants. Although not particularly limited, in some preferred embodiments, from the viewpoint of suppressing the deterioration of the adhesive, the amount of the antioxidant contained in the adhesive layer is, for example, 0.1 parts by weight or more, more preferably 0.5 parts by weight or more, and even more preferably 1 part by weight or more, and may be 2 parts by weight or more, relative to 100 parts by weight of the base polymer. In addition, the amount of the antioxidant can be, for example, about 20 parts by weight or less, and is usually appropriately set to 10 parts by weight or less, and may be set to 5 parts by weight or less.

[0112] (Other ingredients) The pressure-sensitive adhesive layer in the technology disclosed herein may contain one or more rubber-like polymers other than the base polymer, as necessary, to the extent that the effects of the present invention are not significantly impaired. Such rubber-like polymers may be various polymers such as rubber-based, acrylic-based, polyester-based, urethane-based, polyether-based, silicone-based, polyamide-based, and fluorine-based polymers known in the field of pressure-sensitive adhesives. The technology disclosed herein may be preferably implemented in an embodiment in which the pressure-sensitive adhesive layer does not substantially contain a rubber-like polymer other than the base polymer (for example, an embodiment in which the content is 0 to 1 part by weight per 100 parts by weight of the base polymer).

[0113] The adhesive layer in the technology disclosed herein may contain various additives that are common in the field of adhesives, such as leveling agents, crosslinking agents, crosslinking assistants, plasticizers, softeners, fillers, colorants (non-black pigments, dyes, etc.), antistatic agents, UV absorbers, antioxidants, light stabilizers, etc., as necessary. As for such various additives, conventionally known additives can be used in a conventional manner. The adhesive disclosed herein can be preferably implemented in an embodiment that does not substantially contain liquid rubber such as polybutene (for example, the content per 100 parts by weight of the base polymer is 1 part by weight or less, and may be 0 parts by weight). In some preferred embodiments, the adhesive layer may have a composition that does not substantially contain a chelate compound. Here, the chelate compound refers to, for example, a chelate compound of an oxide of an alkaline earth metal and a resin (such as an alkylphenol resin) having a functional group (such as a hydroxyl group, a methylol group, etc.) to which the oxide can be coordinated. The technology disclosed herein can be preferably implemented in an embodiment in which the pressure-sensitive adhesive layer does not contain such a chelate compound at all or the content of the chelate compound is 1 wt % or less. According to such an embodiment, a pressure-sensitive adhesive sheet with superior adhesive strength can be realized.

[0114] In some preferred embodiments, the adhesive layer may have a composition in which the total amount of the base polymer, tackifier resin, and black pigment accounts for 90% by weight or more of the total weight of the adhesive (i.e., the weight of the adhesive layer composed of this adhesive). For example, the total amount of the base polymer, tackifier resin, and black pigment is preferably 95% by weight or more, more preferably 97% by weight or more of the total weight of the adhesive. The effects of the technology disclosed herein are preferably realized by an adhesive layer having the above composition. The upper limit of the total amount of the base polymer, tackifier resin, and black pigment in the adhesive layer may be, for example, 99.9% by weight or less, 99.5% by weight or less, or 99.0% by weight or less.

[0115] (Adhesive composition) The adhesive layer in the technology disclosed herein may be a layer formed from an adhesive composition containing one or more of the above-mentioned components. The form of the adhesive composition disclosed herein is not particularly limited, and may be, for example, an adhesive composition in a form containing an adhesive (adhesive component) having the above-mentioned composition in an organic solvent (solvent-type), an adhesive composition in a form in which the adhesive is dispersed in an aqueous solvent (water-dispersed type, typically aqueous emulsion type), or a hot-melt type adhesive composition. From the viewpoint of impregnation and adhesion to a fibrous substrate, in some embodiments, an adhesive layer formed from a solvent-type adhesive composition is preferred. In some other embodiments, an adhesive layer formed from a hot-melt type adhesive composition is also preferably used. The hot-melt type can be applied in a heat-melted state that does not substantially contain an organic solvent, and is therefore preferred from the viewpoints of productivity and reduction of environmental load.

[0116] The solvent-based pressure-sensitive adhesive composition is typically prepared in the form of a solution containing the above-mentioned components in an organic solvent. The organic solvent can be appropriately selected from known or commonly used organic solvents. For example, any one solvent selected from aromatic compounds (typically aromatic hydrocarbons) such as toluene and xylene; acetate esters such as ethyl acetate and butyl acetate; aliphatic or alicyclic hydrocarbons such as hexane, cyclohexane, and methylcyclohexane; halogenated alkanes such as 1,2-dichloroethane; ketones such as methyl ethyl ketone and acetylacetone; and the like, or a mixture of two or more solvents can be used. Although not particularly limited, it is usually appropriate to prepare the solvent-based pressure-sensitive adhesive composition to a non-volatile content (NV) of 30 to 65% by weight (for example, 40 to 55% by weight). If the NV is too low, the production cost tends to be high, and if the NV is too high, the handling properties such as coatability may be reduced.

[0117] As a method for obtaining a pressure-sensitive adhesive sheet from the pressure-sensitive adhesive composition, various conventionally known methods can be applied. For example, a method (direct method) can be adopted in which the pressure-sensitive adhesive composition is directly applied (typically coated) to a fibrous substrate and dried to form a pressure-sensitive adhesive layer. In addition, a method (transfer method) can be adopted in which the pressure-sensitive adhesive composition is applied to a surface with good releasability (for example, the surface of a release liner) and dried to form a pressure-sensitive adhesive layer on the surface, and the pressure-sensitive adhesive layer is transferred to a fibrous substrate. From the viewpoint of productivity, the transfer method is preferred. The fibrous substrate used in the technology disclosed herein has good impregnation of the pressure-sensitive adhesive, so good properties can be realized even when the transfer method is adopted.

[0118] The adhesive composition can be applied using a known or conventional coater such as a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a bar coater, a knife coater, or a spray coater. From the viewpoint of promoting the crosslinking reaction and improving the production efficiency, it is preferable to dry the adhesive composition under heating. Usually, a drying temperature of about 40°C to 150°C (typically 40°C to 120°C, for example 50°C to 120°C, further 70°C to 100°C) can be preferably adopted. The drying time is not particularly limited, but may be about several tens of seconds to several minutes (for example, about 5 minutes or less, preferably about 30 seconds to 2 minutes). Thereafter, an additional drying step may be provided as necessary. The adhesive layer is typically formed continuously, but may be formed in a regular or random pattern such as a dotted or striped pattern depending on the purpose and use.

[0119] In the adhesive sheet disclosed herein, the thickness of the adhesive layer (in a configuration having a first adhesive layer and a second adhesive layer, the total thickness of the first adhesive layer and the second adhesive layer. The same applies hereinafter unless otherwise specified) is not particularly limited, but is suitably equal to or greater than the thickness of the fibrous substrate, and can be, for example, more than 50 μm. In some preferred embodiments, from the viewpoint of improving adhesive strength, the thickness is more than 65 μm, more preferably more than 75 μm, and even more preferably more than 90 μm. In the adhesive sheet disclosed herein, the adhesive layer is reinforced by a fibrous substrate having an appropriate thickness and density, so that the adhesive properties such as repulsion resistance can be effectively improved by thickening the adhesive layer. In addition, from the viewpoint of the productivity of the adhesive sheet and the cohesive strength of the adhesive layer, in some embodiments, the thickness of the adhesive layer may be, for example, less than 1000 μm, less than 500 μm, less than 250 μm, or less than 200 μm. In some preferred embodiments, the thickness of the adhesive layer is less than 150 μm, less than 140 μm, or less than 135 μm. According to the technology disclosed herein, excellent repulsion resistance, adhesive strength, and cohesive strength can be achieved with a configuration in which the thickness of the adhesive layer is limited as described above. In addition, an adhesive layer with a limited thickness is preferable because it satisfies the demand for thinner and lighter products to which the adhesive sheet is applied.

[0120] In the case of a pressure-sensitive adhesive sheet having pressure-sensitive adhesive layers on both sides of a fibrous substrate, the thickness of each pressure-sensitive adhesive layer may be the same or different. Similarly, the composition of each pressure-sensitive adhesive layer (e.g., pressure-sensitive adhesive type, type and amount of base polymer or tackifier resin, type and amount of crosslinking agent when a crosslinking agent is used, etc.) may be the same or different.

[0121] <Adhesive sheet> The total thickness of the pressure-sensitive adhesive sheet disclosed herein is typically greater than the thickness of the fibrous substrate contained in the pressure-sensitive adhesive sheet. In some embodiments, the total thickness of the pressure-sensitive adhesive sheet may be, for example, 30 μm or more, and from the viewpoint of improving adhesive strength, it is preferably 50 μm or more (e.g., more than 50 μm), more preferably 80 μm or more, even more preferably 100 μm or more (e.g., more than 100 μm), and may be 120 μm or more. In some embodiments, the total thickness of the pressure-sensitive adhesive sheet may be, for example, less than 1000 μm, or may be less than 500 μm. In some preferred embodiments, the total thickness of the pressure-sensitive adhesive sheet is 350 μm or less, more preferably 250 μm or less, even more preferably 200 μm or less, particularly preferably 180 μm or less, may be 160 μm or less, or may be 150 μm or less (e.g., less than 150 μm). According to the technology disclosed herein, excellent repulsion resistance, adhesive strength, and cohesive strength can be achieved with a configuration in which the total thickness of the pressure-sensitive adhesive sheet is limited as described above. Furthermore, a pressure-sensitive adhesive sheet with a limited thickness is preferable since it satisfactorily meets the demand for thinner and lighter products to which the pressure-sensitive adhesive sheet is applied.

[0122] Also, the total thickness of the adhesive sheet disclosed herein is typically 1.1 times or more, for example 1.5 times or more, of the thickness of the fibrous substrate contained in the adhesive sheet. In some preferred embodiments, from the viewpoint of improving adhesive properties such as repulsion resistance, the total thickness of the adhesive sheet is 2.0 times or more, more preferably 2.5 times or more, and even more preferably 3.0 times or more (for example, more than 3.0 times) of the thickness of the fibrous substrate. Also, in some embodiments, the total thickness of the adhesive sheet may be, for example, 30 times or less, 20 times or less, 10 times or less, 6.0 times or less, 5.0 times or less, or 4.0 times or less of the thickness of the fibrous substrate.

[0123] Although not particularly limited, in some embodiments, the 180 degree peel strength (adhesive strength) of the adhesive sheet against a stainless steel plate is preferably 20N / 20mm or more. An adhesive sheet having the above adhesive strength can exhibit high adhesion performance against various adherends, such as metals and polar adherends. Furthermore, in an adhesive sheet having the above adhesive strength, the repulsion resistance is preferably achieved by the technology disclosed herein. The above adhesive strength is more preferably 24N / 20mm or more, even more preferably 26N / 20mm or more, and particularly preferably 27N / 20mm or more. Furthermore, the upper limit of the above adhesive strength is determined by the required L. * In relation to this, it may be, for example, 50 N / 20 mm or less, 40 N / 20 mm or less, or 35 N / 20 mm or less. The adhesive strength of the pressure-sensitive adhesive sheet is the 180-degree peel strength against a stainless steel plate measured under conditions of 23°C, 50% RH, and a tensile speed of 300 mm / min, and more specifically, is measured by the method described in the Examples below.

[0124] Although not particularly limited, in some embodiments, the pressure-sensitive adhesive sheet preferably has a slippage distance of less than 1.0 mm after a holding power test performed under conditions of a load of 500 g, an adhesion area of ​​10 mm x 20 mm, 70°C, and 1 hour. Since the pressure-sensitive adhesive sheet having the above holding power characteristics has high cohesive strength, it can be preferably used as a pressure-sensitive adhesive sheet with good adhesion reliability. In some preferred embodiments, the slippage distance is 0.9 mm or less, may be 0.8 mm or less, or may be 0.7 mm or less. The holding power test is performed in detail by the method described in the Examples below.

[0125] <Application> The adhesive sheet disclosed herein can be preferably used for bonding and fixing members contained in various products such as office automation equipment, home appliances, and automobiles. The adhesive sheet disclosed herein can stably maintain repulsion resistance that makes it difficult to peel off from a curved surface, and is therefore preferably used, for example, in an embodiment in which it is attached to an area including a curved surface of an adherend having a curved surface. In addition, when the adherend is a black adherend, due to the high blackness of the adhesive layer, the adhesive sheet is not noticeable on the adherend to which the adhesive sheet is attached, and the appearance is not impaired. For example, when the adhesive sheet is used to bond and fix members, one or both of the two adherend members may be colored black. Such a black adherend is preferably a black adherend having a black L at the place where the adhesive sheet is attached and in the vicinity thereof. * The above L includes those having a blackness of 10 or less. * can be measured using a color difference meter (product name "X-rite eXact, manufactured by X-Rite Inc."). Although not particularly limited, one suitable example of the use of the adhesive sheet disclosed herein is an application for fixing the housing and cushion part of a black head mounted display. Usually, the housing is molded from a plastic material, and the cushion part is formed from a foam material. The cushion part is for bringing the head and the head mounted display main body into close contact without light leakage, and both the housing and the cushion part have three-dimensional shapes with curved surfaces. The adhesive sheet is used to fix both the housing and the cushion part at the curved surfaces of the housing and the cushion part.

[0126] In addition, the adhesive sheet disclosed herein is suitable for various applications that require light-shielding properties.For example, some electronic devices such as portable electronic devices contain light-emitting elements for the purpose of image display, etc., so the adhesive sheet may be required to have light-shielding properties in order to prevent light leakage and light reflection.The adhesive sheet disclosed herein is suitable for such electronic devices.

[0127] Non-limiting examples of the portable electronic device include mobile phones, smartphones, tablet computers, notebook computers, various wearable devices (for example, wristwear type devices worn on the wrist like a wristwatch, modular type devices worn on a part of the body with a clip or strap, eyewear type devices including glasses (monocular type and binocular type devices, including head-mounted type devices), clothing type devices attached to shirts, socks, hats, etc. in the form of accessories, earwear type devices attached to the ears like earphones, etc.), digital cameras, digital video cameras, audio devices (portable music players, IC recorders, etc.), calculators (calculators, etc.), portable game devices, electronic dictionaries, electronic organizers, electronic books, in-vehicle information devices, portable radios, portable televisions, portable printers, portable scanners, portable modems, etc. In this specification, "portable" does not mean that it is sufficient to simply be portable, but rather that it has a level of portability that allows an individual (average adult) to carry it relatively easily. Examples of the electronic device include personal computers (desktop type, notebook type, tablet type, etc.), televisions, etc. These may incorporate a display device such as a liquid crystal or organic electro-luminescence (EL) display device.

[0128] The pressure-sensitive adhesive sheet disclosed herein can have excellent light-shielding properties, and is therefore preferably used in electronic devices that include various light sources such as LEDs (light emitting diodes) and light-emitting elements such as self-emitting organic EL. For example, it can be preferably used in electronic devices (typically mobile electronic devices) equipped with liquid crystal display devices that require specific optical characteristics. More specifically, it can be preferably used in liquid crystal display devices equipped with a liquid crystal display module unit (LCD unit) and a backlight module unit (BL unit). EXAMPLES

[0129] Some examples of the present invention will be described below, but it is not intended that the present invention be limited to those shown in these examples. In the following description, "parts" and "%" are by weight unless otherwise specified.

[0130] <Example 1> (Preparation of Pressure-Sensitive Adhesive Composition) 100 parts of styrene-isoprene block copolymer as a base polymer (manufactured by Zeon Corporation, product name "Quintac 3520", styrene content 15%, diblock ratio 78%), 30 parts of aromatic petroleum resin (manufactured by ENEOS Corporation, product name "Nippon Oil Neopolymer 150", softening point 155 ° C., hydroxyl value less than 1 mg KOH / g), 40 parts of terpene phenol resin, 20 parts of terpene resin, 0.75 parts of isocyanate compound (manufactured by Mitsui Chemicals, Inc., product name "Takenate D-101E") on a non-volatile content (NV) basis, 3 parts of antioxidant, 4 parts of black pigment dispersion on a NV basis, and toluene as a solvent were stirred and mixed to prepare a pressure-sensitive adhesive composition with NV 50%. Here, two types of terpene phenol resins, "YS Polystar S145" (softening point 145°C, hydroxyl value 100mgKOH / g) and "YS Polystar T145" (softening point 145°C, hydroxyl value 60mgKOH / g) manufactured by Yasuhara Chemical Co., Ltd., were used in a weight ratio of 1:1, with a total of 40 parts. The terpene resin used was "YS Resin PX1150N" (softening point 115°C, hydroxyl value less than 1mgKOH / g) manufactured by the same company. The antioxidant used was "IRGANOX CB612" manufactured by BASF (a blend of "IRGAFOS 168" and "IRGANOX 565" manufactured by BASF in a weight ratio of 2:1). The black pigment dispersion used contained 30% carbon black (average particle size: approximately 0.2 μm), 65% liquid resin (viscosity: 4000 to 6600 mPa·s), and 5% other dispersants.

[0131] (Preparation of adhesive sheet) A sheet-like release liner was prepared by laminating a 25 μm-thick polyethylene layer on one side of fine paper and subjecting the layer to a release treatment using a silicone-based release agent. The adhesive composition obtained above was applied to the release-treated surface of the release liner and dried to form an adhesive layer with a thickness of 64 μm on the release liner. This adhesive layer was transferred to a first surface of a substrate to form a first adhesive layer. In the same manner, a second adhesive layer was formed on a second surface of the substrate. The substrate had a basis weight of 14 g / m2. 2 , thickness 42μm, density 0.33g / cm 3 A nonwoven fabric of the above was used. As described above, a laminate was obtained in which the first adhesive layer and the second adhesive layer were laminated on the first and second surfaces of the substrate, respectively, and the surface of each adhesive layer was protected by the release liner. Then, this laminate was passed through a laminator under predetermined pressure, speed and temperature conditions, and cured for 1 hour in an environment of 23°C, to produce a double-sided adhesive sheet (double-sided adhesive sheet with substrate) with a total thickness of 140 μm.

[0132] <Examples 2 to 5 and Comparative Examples 1 to 3> The amount of black pigment dispersion added to the adhesive composition and the type of substrate were changed as shown in Table 1. Otherwise, the adhesive sheets of each example were produced in the same manner as in the production of the adhesive sheet of Example 1. In Example 5, a 17.5 g / m2 substrate with a basis weight of 1.5 g / m2 was used. 2 , thickness 45μm, density 0.39g / cm 3 In Comparative Example 2, a nonwoven fabric having a basis weight of 16 g / m was used as the substrate. 2 , thickness 35μm, density 0.46g / cm 3 The nonwoven fabric was used.

[0133] <Evaluation method> (L * value) The L of the pressure-sensitive adhesive layer according to each example * The value was measured using a color difference meter based on JIS Z8781-4:2013. Specifically, with the second surface side protected by a release liner, the adhesive layer was set at the measurement position, and the L * The values ​​were measured.

[0134] (SS breaking strength) The adhesive layer according to each example was cut into a size of 15 mm in the machine direction (MD) and 40 mm in the transverse direction (TD) together with the release liner, and the adhesive layer was rolled in the TD direction and rolled into a cylindrical shape to prepare a measurement sample. In an environment of 23°C and 50% RH, both ends of the cylindrical measurement sample were clamped with chucks and set in a tensile tester (Minebea Co., Ltd., universal tensile compression tester, device name "tensile compression tester, TCM-1kNB"), and the measurement sample was pulled under the conditions of a chuck distance of 10 mm and a pulling speed of 50 mm / min. From the obtained stress-strain curve (SS curve), the strength at the time of breakage of the measurement sample (initial SS breaking strength) [MPa] was obtained. The SS breaking strength [MPa] was measured in the same manner as for the initial SS breaking strength, except that the adhesive layer was aged for 4 weeks in an environment of 60°C and 90% RH as the adhesive layer to prepare the measurement sample. This was defined as the SS breaking strength after storage at high temperature and high humidity.

[0135] (Repulsion resistance) The adhesive sheet (double-sided adhesive sheet) was cut to a size of 20 mm wide and 180 mm long, and the first release liner was peeled off to expose the first adhesive surface, and an aluminum plate with a thickness of 0.5 mm cut to the same size was attached to the first adhesive surface to prepare a test specimen. This test specimen was pressed onto a 2 mm thick polypropylene (PP) plate cut to a size of 30 mm x 200 mm using a laminator in an environment of 23 ° C and 50% RH, and then kept in the same environment for 24 hours. Next, as shown in Figure 2, the PP plate with the test specimen attached was warped into an arc shape with a chord length of 190 mm using a jig with a U-shaped cross section. This was kept in an atmosphere of 70 ° C for 72 hours, and the distance h [mm] by which the end of the test specimen rose from the surface of the PP plate was measured (Figure 3). This was taken as the repulsion resistance (initial). In addition, in Figs. 2 and 3, the reference numerals 100, 200, 300, and 400 respectively indicate the double-sided pressure-sensitive adhesive sheet excluding the first and second release liners, the aluminum plate, the PP plate, and the jig. In addition, the repulsion resistance [mm] was measured in the same manner as in the above-mentioned repulsion resistance (initial) except that the test specimen was aged for 4 weeks in an environment of 60°C and 90% RH. This was defined as the repulsion resistance (after 4 weeks at 60°C and 90% RH). In both the evaluations of the repulsion resistance (initial) and the repulsion resistance (after 4 weeks at 60°C, 90% RH), if the lift distance h was 7.0 mm or less, it was judged as pass (◯), and if the lift distance h was more than 7.0 mm, it was judged as fail (×).

[0136] (Appearance evaluation) The adhesive sheet with release liner was cut to a size of about 50 mm x 50 mm, and a 25 μm thick polyethylene terephthalate (PET) film (product name "Lumirror #25 S10", manufactured by Toray Industries, Inc.) was attached to the second adhesive surface exposed by peeling off the release liner to prepare a measurement sample. This measurement sample was placed on top of five sheets of white paper (manufactured by Smart Value Co., Ltd., product number "A032J") with the PET film side facing down, and the color was visually confirmed. Next, the measurement sample was removed from the top of the white paper, and black origami paper (manufactured by Toyo Co., Ltd., product name "Monochrome Origami (Black)") was placed on top of the white paper, and the color was visually confirmed. Then, the color of the measurement sample was compared with that of the black origami paper, and if the color of the measurement sample and the black origami paper were felt to be the same or if the measurement sample was felt to be a darker black, a score of 1 (pass) was given, and if the measurement sample was felt to be a lighter black, a score of 0 (fail) was given. The above evaluation was carried out by 10 people in their 20s to 50s with no color vision deficiencies. A total score of 7 points or more was judged as a pass (O), and a score of less than 7 points was judged as a fail (X).

[0137] (Adhesive strength) The release liner covering one adhesive surface of the adhesive sheet (double-sided adhesive sheet) was peeled off, and a 25 μm thick PET film was attached to the backing. The backed adhesive sheet was cut to a size of 20 mm wide and 100 mm long to prepare a test piece. In an environment of 23°C and 50% RH, the release liner covering the other adhesive surface of the test piece was peeled off, and the test piece was pressed against the surface of a stainless steel plate (SUS304 plate) as an adherend by rolling it back and forth once with a 2 kg roller. After leaving it in the same environment for 30 minutes, the 180° peel adhesion strength [N / 20 mm] was measured using a tensile tester at a tensile speed of 300 mm / min in accordance with JIS Z 0237. The measurement was performed three times (i.e., N=3), and the arithmetic average value was calculated. In the case of a single-sided adhesive sheet, the backing of the PET film is not necessary.

[0138] (70℃ holding power) The release liner covering one adhesive surface of the adhesive sheet (double-sided adhesive sheet) was peeled off, and the adhesive sheet was attached to a PET film having a thickness of 25 μm for backing. The backed adhesive sheet was cut to a size of 10 mm wide and 100 mm long to prepare a measurement sample. The release liner covering the other adhesive surface of the measurement sample was peeled off, and the other adhesive surface was pressed against a stainless steel plate (SUS304 plate) as an adherend with a bonding area of ​​10 mm wide and 20 mm long by a 2 kg roller moving back and forth once. The measurement sample thus attached to the adherend was then hung down in an environment at 70 ° C. and left for 30 minutes, and a load of 500 g was applied to the free end of the measurement sample, and the measurement sample was left in an environment at 70 ° C. for 1 hour with the load applied, and the deviation distance (mm) from the initial attachment position of the measurement sample was measured according to JIS Z0237.

[0139] The outline of each example and the evaluation results are shown in Table 1.

[0140] [Table 1]

[0141] As shown in Table 1, the pressure-sensitive adhesive sheets according to Examples 1 to 5 had a L of the pressure-sensitive adhesive layer. *10 or less, the SS breaking strength after aging for 4 weeks in an environment of 60°C and 90% RH (SS breaking strength after storage at high temperature and high humidity) is within the range of 0.70 to 1.10 MPa, and the density of the base material is 0.4 g / cm 3 The results of the appearance and repulsion resistance evaluations were acceptable. On the other hand, the amount of black pigment blended was low, and the L * In Comparative Example 1, the appearance evaluation was unacceptable because the density was more than 10. 3 Comparative Example 2, which used a substrate of 1000g, was evaluated as passing the repulsion resistance (initial stage), but failed the repulsion resistance evaluation after aging at 60°C and 90% RH for 4 weeks, and was unable to stably maintain the repulsion resistance. Comparative Example 3, which had a large amount of black pigment and an SS breaking strength of the adhesive layer after high temperature and high humidity storage of less than 0.70 MPa, was also evaluated as passing the repulsion resistance (initial stage), but failed the repulsion resistance evaluation (after 4 weeks at 60°C and 90% RH), and was unable to stably maintain the repulsion resistance. In particular, in comparison between Example 1 and Comparative Example 2, which used the same type of adhesive layer but different substrates, in Comparative Example 2, the adhesive layer had high cohesive strength based on the high initial SS breaking strength value, so the expression of initial repulsion resistance performance due to the high cohesive strength was dominant over the effect of the decrease in the impregnation of the adhesive to the high-density substrate, but as a result of the deterioration of the adhesive layer and the decrease in cohesive strength due to the aging at 60°C and 90% RH for 4 weeks, the effect of the decrease in repulsion resistance due to the decrease in the impregnation of the adhesive prevailed, and it is considered that the repulsion resistance after aging at 60°C and 90% RH for 4 weeks was significantly decreased. Although not specifically shown in the examples, when the adhesive strength and holding strength of the adhesive sheet after aging at 60°C and 90% RH for 4 weeks were evaluated, no significant difference was observed between Example 1 and Comparative Example 2. From these results, it is considered that the effect of aging at 60°C and 90% RH for 4 weeks was significantly observed in the characteristics in the long-term and low-speed range (specifically, the repulsion resistance evaluated by the above method). From the above experimental results, it can be understood that there is a high correlation between the cohesive strength (specifically, SS breaking strength) of the adhesive layer after aging at 60°C and 90% RH for 4 weeks and the repulsion resistance after aging at 60°C and 90% RH for 4 weeks, and the impact on repulsion resistance of the difference in adhesive impregnation based on the difference in substrate density between Example 1 and Comparative Example 2.

[0142] From the above results, it is considered that the present invention is a pressure sensitive adhesive sheet having a fibrous base material and a pressure sensitive adhesive layer provided on at least one surface of the fibrous base material, and the density of the fibrous base material is 0.4 g / cm 3 The adhesive layer is L * a * b * L defined in the color system * According to a pressure-sensitive adhesive sheet having a surface roughness of 10 or less and a breaking strength of 0.70 MPa or more and 1.10 MPa or less in a tensile test performed at 23°C and a tensile speed of 50 mm / min after being kept in an environment of 60°C and 90% RH for 4 weeks, it is clear that the pressure-sensitive adhesive sheet has a configuration including a fibrous base material, which can impart a good appearance due to the high blackness of the pressure-sensitive adhesive layer, and can stably maintain good repulsion resistance even when exposed to a harsh environment based on the selection of the fibrous base material and the above-mentioned SS breaking strength characteristics of the pressure-sensitive adhesive layer after storage at high temperature and high humidity.

[0143] Although specific examples of the present invention have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and changes of the specific examples exemplified above. [Explanation of symbols]

[0144] 1 Adhesive sheet 11 First adhesive layer 11A 1st adhesive side 12 Second adhesive layer 12A 2nd adhesive side 15 Fibrous base material 21 Release Liner 21B Back

Claims

1. The present invention comprises a fibrous base material and a pressure-sensitive adhesive layer provided on at least one surface of the fibrous base material, The density of the fibrous base material is 0.4 g / cm 3 is as follows: The pressure-sensitive adhesive layer is L * a * b * L defined by the color system * is 10 or less, A pressure-sensitive adhesive sheet, which, after being kept in an environment of 60°C and 90% RH for 4 weeks, has a breaking strength of 0.70 MPa or more and 1.10 MPa or less in a tensile test carried out under conditions of 23°C and a tensile speed of 50 mm / min.

2. The pressure-sensitive adhesive sheet according to claim 1 , wherein the pressure-sensitive adhesive layer contains a black pigment dispersion.

3. The pressure-sensitive adhesive sheet according to claim 2 , wherein the black pigment dispersion contains a black pigment and a liquid resin, and at least a portion of the black pigment is dispersed in the liquid resin.

4. 4. The pressure-sensitive adhesive sheet according to claim 2, wherein the black pigment dispersion is blended in an amount of 4 parts by weight or more and 10 parts by weight or less based on non-volatile content, relative to 100 parts by weight of the base polymer contained in the pressure-sensitive adhesive layer.

5. The pressure-sensitive adhesive sheet according to any one of claims 1 to 3, wherein the pressure-sensitive adhesive layer contains a rubber-based polymer as a base polymer.

6. The pressure-sensitive adhesive sheet according to any one of claims 1 to 3, wherein the pressure-sensitive adhesive layer contains a styrene-based block copolymer as a base polymer.

7. The pressure-sensitive adhesive sheet according to any one of claims 1 to 3, wherein the pressure-sensitive adhesive layer is a pressure-sensitive adhesive layer formed from a solvent-type pressure-sensitive adhesive composition or a hot-melt type pressure-sensitive adhesive composition.

8. The pressure-sensitive adhesive sheet according to any one of claims 1 to 3, wherein the fibrous base material has a thickness of 20 µm or more and 60 µm or less.

9. The pressure-sensitive adhesive sheet according to any one of claims 1 to 3, wherein the pressure-sensitive adhesive sheet has a total thickness of 100 µm or more and 350 µm or less.

10. The pressure-sensitive adhesive sheet according to any one of claims 1 to 3, which is attached to a region of a black adherend having a curved surface, the region including the curved surface.

Citation Information

Patent Citations

  • Adhesive composition and adhesive sheet

    JP2015028130A

  • Adhesive sheet and display body

    JP2020007500A